Prendre soin de sa santé psychologique en culture avec Florence Morin-Parent, psychologue (Le répondeur de l'industrie musicale, 2024)
Keywords: Bibliographie; Nettoyer

Cultive, la plateforme du développement professionnel en culture (Cultive, 2024)
Plateforme qui rassemble les offres de formation, les outils et les références pour le développement de votre carrière en culture au Québec.
Keywords: Bibliographie; Nettoyer

Safia Nolin répond à la haine par la musique - Caillou, Annabelle (Le Devoir, 2024)
Se gardant de tout révéler, l’artiste explique qu’elle sera sur scène avec pour seules armes sa guitare et sa voix.
Keywords: Bibliographie; Nettoyer

Condamnation pour agression sexuelle: Goûchy Boy lance sa marchette sur les journalistes avant de recevoir sa peine - Perron, Louis-Samuel (La Presse, 2024)
Deux heures après avoir attaqué un photographe de presse en lui lançant sa marchette en plein palais de justice, le comédien Goûchy Boy a été condamné à 21 mois d’emprisonnement, mercredi, pour avoir agressé sexuellement une femme qu’il traitait comme son « objet sexuel ».

High time to enhance dancer welfare: a call to action to improve safeguarding and abuse prevention in dance - Cumming, Jennifer; Nordin-Bates, Sanna M.; Johnson, Carrie; Sanchez, Erin N.; Karageanes, Steven J. (BMJ Open Sport & Exercise Medicine, 2024)
While there is a lack of research into abuse in elite dance, numerous allegations of emotional, sexual and physical abuse of dancers can be found anecdotally in the media, legal convictions and personal accounts. As more dancers speak out, the scale of the problem within preprofessional schools and professional companies is becoming apparent. Accordingly, effective safeguarding mechanisms for preventing, identifying and reporting abuse are urgently needed. This viewpoint is intended to raise health professionals’ awareness of factors contributing to abusive practices found in dance environments and the potential clinical implications of abuse to dancers’ health and well-being. We also call for research and policy engagement on safeguarding and abuse prevention designed and implemented in partnership with stakeholders, aiming to promote safe and positive dance environments for all.

Le Centre psychologique pour artistes, un nouvel outil pour le milieu culturel - Renaud, Philippe (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

“Quelque chose a changé dans cette si masculine République des Lettres”. Tribune - d'Academia, L'équipe des rédacteurs (Academia, 2024)
Academia reproduit un tribune publiée dans Le Monde daté du 8 mars 2024 sous le titre Violences sexuelles. « Ce qui se passe dans le milieu du cinéma se passe aussi ailleurs, à l’université, dans les écoles, dans l’édition ». Plusieurs membres … Continuer la lecture →

Centre d'aide aux victimes d'actes criminels (CAVAC, 2024)
«Le Réseau des CAVAC est présent dans toutes les régions du Québec. Plus de 185 portes qui vous donnent accès à des professionnel(le)s formé(e)s en intervention ».
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Californie: Un professeur de musique de McGill poursuivi pour agression sexuelle - Siag, Jean (La Presse, 2024)
Un professeur de musique de l’Université McGill est poursuivi au civil aux États-Unis par deux anciennes étudiantes disant avoir été agressées sexuellement à l’époque où il enseignait en Californie. Des allégations que le professeur nie vigoureusement.
Keywords: Bibliographie; Nettoyer

Mémoire présenté à la Commission de l’économie et du travail Dans le cadre des consultations particulières et des auditions publiques sur le projet de loi n° 42 - Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail - Juripop (2024)
Keywords: Bibliographie; Nettoyer

Les agressions sexuelles : de quoi parle-t-on? - INSPQ (Institut national de santé publique du Québec, 2024)
Il n’existe pas de définition universelle de l’agression sexuelle, et différentes perspectives peuvent être utilisées pour la définir (p. ex. politique, légale, clinique ou scientifique). Un élément commun à toutes les formes d’agression sexuelle est l’absence de consentement, c’est-à-dire que la personne victime n’a pas consenti à l’activité sexuelle ou à la poursuite de celle‑ci, qu’elle était incapable d’y consentir ou de la refuser ou qu’elle n’avait pas l’âge de consentir.
Keywords: Coffre à outils; À ajouter

Rethinking sexual violence labels: exploring the impact of ‘victim’ and ‘survivor’ discourse - O’Shea, Brittany; Feicht, Rebecca; Brown, Marion; Numer, Matthew (European Journal of Psychotraumatology, 2024)
Background: Universities’ responses to sexual violence have faced scrutiny for their lack of proactiveness and their failure to address campus socio-cultural norms that contribute to rape myth acceptance. The labels victim and survivor play a crucial role in shaping attitudes toward sexual violence, but there is limited research on how university students perceive these labels. Objective: This paper explores sexual violence labels and their role in perpetuating rape culture. Undergraduate university students’ beliefs on using the label survivor instead of victim to describe someone who has experienced sexual violence were examined to consider how these labels create societal discourse on sexual violence. Method: The study draws on qualitative data collected from undergraduate students in Canada and the United States through open-response questions in an interactive textbook. Data were analysed and interpreted using a multi-method approach that combined principles of Critical Discourse Analysis and Feminist Poststructuralism. Direct quotes and word clouds from participants’ responses are used as evidence and to visually display discourse. Results: Findings revealed that participants recognised the negative societal discourses associated with the label victim and supported using survivor to challenge perceptions of sexual violence. Despite this, participants expressed hesitancy to adopt the label survivor because of the potential negative implications, such as the label promoting the allocation of individual blame, increasing barriers to justice, and reducing the perceived severity of sexual violence. Conclusions: This study underscores the complexities of sexual violence labels, the influence of language in shaping societal perceptions, and the need for a more comprehensive and equitable approach to responding to sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence.Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence.Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence. Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence. Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence.
Keywords: Bibliographie; Nettoyer

Code de conduite [Affiche] (2024)
18 x 24 harcèlement affiche WEB
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Déclaration pour un environnement de travail exempt de harcèlement dans le milieu culturel québécois (Regroupement des arts interdisciplinaires du Québec, 2024)
ATTENDU QUE des associations d’artistes et des associations de producteurs (ci-après collectivement les « Associations ») ainsi que les regroupements du milieu culturel (ci-après collectivement les « Regroupements »), conviennent que toutes les personnes œuvrant dans le milieu culturel québécois, quel que ce soit leur rôle ou leurs responsabilités, devraient être en mesure d’exercer [...]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Dénoncez un incident sur le plateau (ACTRA Montreal, 2024)
Grâce aux rapports anonymes, nous sommes informés des problèmes au fur et à mesure qu’ils surviennent. Il est possible de rester anonyme, mais il est préférable de laisser vos coordonnées pour que nous puissions vous contacter. Nous ne donnerons jamais suite à une réclamation sans votre consentement!
Keywords: Bibliographie; Nettoyer

En mouvement vers une culture du consentement (RQCALACS, 2024)
Les CALACS offrent des services de soutien aux victimes d’agressions à caractère sexuel. Trouvez de l’aide, partout à travers le Québec.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

J'ai besoin d'un avocat - Services offerts aux organismes (Juripop, 2024)

le relationnel (le relationnel, 2024)
Ressource suggéré par REPAIRE : « Le relationnel, service de thérapie en relation d'aide. Nos thérapeutes vous accompagnent sur le chemin de votre développement personnel, à votre rythme. »

Léa et Loïc (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Nettoyer

Services (Divergenres, 2024)
Keywords: Coffre à outils; À ajouter

Tous les spectacles (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Violences conjugales et sexuelles: Formations gratuites (Juripop, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Coordonnateur·rice·s de l'intimité - ACTRA Montréal (ACTRA Montreal, 2024)
Les coordonnateurs d'intimité sont des spécialistes de la production qui planifient, supervisent et coordonnent les scènes intimes filmées.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Contribuer à une culture exempte de harcèlement (SST) - AQTIS 514 IATSE (L'Alliance québécoise des techniciens et techniciennes de l'image et du son, section locale 514, 2024)
« Parce que la sécurité au travail est une responsabilité collective, luttons ensemble pour éliminer le harcèlement ! Votre syndicat a fait de cet enjeu sa priorité. Notre industrie, atypique et fortement compétitive, peut engendrer de nombreux abus et freiner la dénonciation. La précarité d'emploi, la hiérarchisation des fonctions, le taux de rendement exigé, le niveau de stress et la crainte de représailles en sont les principaux facteurs. L'AQTIS 514 IATSE met à votre disposition une formation gratuite et interactive pour vous aider à travailler dans un environnement sécuritaire. OBJECTIFS : Reconnaître les situations qui s’apparentent à du harcèlement psychologique ou sexuel au travail; Savoir adopter une posture d’affirmation face à des conduites d’incivilité, d’intimidation ou de harcèlement en vue de les faire cesser; Connaître les mécanismes pour signaler ou dénoncer les conduites s’apparentant à de l’intimidation ou du harcèlement.»
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

L'intimidation et la cyberintimidation au Québec: portrait à partir de l'Étude québécoise sur les rapports sociaux dans un contexte scolaire, de travail et dans la communauté 2022 - Aranibar Zeballos, Daniela; Paquette, Jesseca (Institut de la statistique du Québec, 2024)
Keywords: Bibliographie; Nettoyer

Violence sexuelle - Bureau de la médiation et du signalement (Université McGill, 2024)
Tous les membres de McGill ont droit au soutien sans équivoque du Bureau d’intervention, de prévention et d’éducation en matière de violence sexuelle (OSVRSE – Office for Sexual Violence Response, Support, and Education), que ces membres déposent ou non un signalement officiel. L’OSVRSE peut vous fournir des services de soutien, vous aider à obtenir des accommodements scolaires ou professionnels et vous expliquer les différents processus de signalement — que vous envisagiez de faire un signalement dans le cadre de la Politique contre la violence sexuelle de McGill ou à l’extérieur — afin que vous puissiez décider ce qui vous convient le mieux. Il n’est pas nécessaire de déposer un signalement officiel pour accéder à du soutien, demander des accommodements possibles ou obtenir de l’information auprès de l’OSVRSE. Vous pouvez prendre rendez-vous directement avec l’OSVRSE ici. Si vous souhaitez déposer un signalement en vertu de la Politique contre la violence sexuelle de McGill ou en apprendre davantage au sujet des processus offerts (médiation/enquête), veuillez communiquer avec le Bureau de la médiation et du signalement (OMR). Visitez notre page Demander une consultation pour en savoir plus. Tous les membres de la communauté universitaire ont le droit de travailler et d’apprendre dans un environnement exempt de violence sexuelle. L’Université reconnaît que, même si la violence sexuelle touche tous les membres de la société, ce type de maltraitance et ses conséquences peuvent atteindre de manière disproportionnée des membres de groupes sociaux aux prises avec des formes intersectionnelles de discrimination systémique ou d’obstacles (fondés notamment sur l’identité et l’expression sexuelles, l’orientation sexuelle, la race, la religion, l’appartenance à un groupe autochtone, l’ethnicité, l’invalidité ou la classe sociale).  Qu’est-ce que la violence sexuelle ? La violence sexuelle est un terme générique qui désigne un continuum d’actes de nature sexuelle qui sont menacés, tentés ou commis à l’encontre d’une personne sans son consentement. Elle peut être dirigée vers l’orientation sexuelle, l’expression sexuelle ou de genre ou l’identité de genre d’une personne. Cela inclut l’agression sexuelle, le harcèlement sexuel, le harcèlement criminel, la cyberviolence, la distribution non consensuelle d’images sexuelles, le voyeurisme, etc. L’OSVRSE de McGill présente de plus amples renseignements sur la violence sexuelle sur son site Web. Définition dans la politique La définition officielle de la violence sexuelle adoptée à McGill se trouve à l’alinéa 7k) de la Politique contre la violence sexuelle de McGill : « Violence sexuelle » s’entend d’un ou de plusieurs actes sexuels, commis ou tentés, qui ciblent la sexualité, l’identité ou l’expression sexuelle d’une personne, ou toute menace de commettre de tels actes contre une personne sans son consentement. La violence sexuelle peut se manifester en personne, au téléphone ou en ligne. Elle englobe : i) l’agression sexuelle qui désigne un contact sexuel avec une autre personne sans son consentement; ii) le harcèlement sexuel, qui désigne une conduite de nature sexuelle A) selon laquelle l’activité sexuelle : est établie comme modalité ou condition explicite ou implicite d’emploi d’une personne ou de statut dans un cours, un programme ou une activité; ou  est utilisée comme motif sous-tendant une décision en matière d’emploi ou d’éducation qui a des incidences sur une personne; OU, B) qui a pour effet de nuire au travail ou au rendement universitaire d’une personne quand il est reconnu, ou devrait être reconnu, que cette conduite est importune;  iii) « traquer » qui désigne la surveillance ou le fait de suivre indûment une autre personne alors que cette personne, déposant une divulgation ou un signalement, a l’impression que cette traque a un lien avec le sexe ou l’identité sexuelle; iv) « exhibitionnisme » qui désigne l’exposition de ses organes sexuels à une autre personne dans un lieu public ou de manière menaçante ou choquante pour cette personne; v) « voyeurisme » qui désigne l’observation furtive ou l’enregistrement d’une personne au moyen d’un dispositif mécanique ou électronique; vi) « diffusion d’images sexuelles » qui désigne la distribution d’une image, photo ou vidéo de nature sexuelle d’une personne sans son consentement; et vii) « exploitation sexuelle » qui désigne l’abus ou l’exploitation de la sexualité d’une autre personne aux fins d’une gratification sexuelle, d’un gain pécuniaire, d’un avantage personnel ou à tout autre fin non légitime.
Keywords: Bibliographie; Nettoyer

Impact de la violence sexuelle sur la santé mentale - Centre d’Innovation en Santé Mentale sur les campus (2024)
Keywords: Bibliographie; Nettoyer

Salut ça va ? Dialoguer pour prévenir les violences sexuelles - Clermont-Dion, Léa (Cardinal, 2024)
Dans cet essai coup-de-poing, Léa Clermont-Dion s’adresse d’abord aux adolescents et aux jeunes adultes, à leurs parents et à leurs professeur.es, pour ouvrir la discussion sur les violences à caractère sexuel. Son but : éduquer et sensibiliser pour parvenir à des rapports humains respectueux et égalitaires, toujours en évitant de blâmer qui que ce soit. L’autrice vulgarise les concepts de consentement, de culture du viol, de masculinité toxique et explore la portée du mouvement #MeToo. Elle échange aussi avec des acteurs-clé du monde du sport, dont Laurent Duvernay-Tardif, ainsi qu’avec des intervenants du système de justice et recueille de bouleversants témoignages de victimes.
Keywords: Bibliographie; Nettoyer

Modèle de politique en matière de harcèlement psychologique ou sexuel au travail et de traitement des plaintes - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2024)
Notre modèle de politique est présentement en cours de révision pour tenir compte des nouvelles dispositions prévues par la Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail
Keywords: Bibliographie; Nettoyer

Justice réparatrice en matière de violence conjugale : Enjeux et recommandations - Conseil du statut de la femme (2024)
Keywords: Bibliographie; Nettoyer

Accueil - CRIPCAS (2024)
Centre de recherche interdisciplinaire sur les problèmes conjugaux et les agressions sexuelles
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Intermittents du spectacle - France Travail (2024)
Keywords: Bibliographie; Nettoyer

GRIP-Prévention - Groupe de recherche et d'intervention psychosociale (GRIP, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collections - Groupe de recherche et d'intervention psychosociale (GRIP) (GRIP, 2024)
Le GRIP intervient en milieu festif (rave, festival) afin de réduire les méfaits associés à la consommation de drogues et de prévenir ses usages problématiques.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Il était une fois... de trop - Institut national de l'image et du son. (2024)
Une formation pour prévenir le harcèlement en culture.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les professions de la culture et des communications au Québec en 2021 - Lubin, Marc-Ancy (Optique culture, 2024)
Keywords: Bibliographie; Nettoyer

Michel Venne devra finalement prendre le chemin de la prison - Marin, Stéphanie (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Faire justice. Moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Marsault, Elsa Deck (Les Éditions du remue-ménage, 2024)

#UsToo: how Jewish, Muslim, and Christian women changed our communities - McGinity, Keren R. (Routledge, Taylor & Francis Group, 2024)
"#UsToo: How Jewish, Muslim, and Christian Women Changed Our Communities examines the relationship between sexual harassment, gender, and multiple religions, highlighting the voices of women of different faiths who found their voices and used them for the betterment of their communities. Through personal interviews and other research, this book explores the actions of American Jewish, Muslim, and Christian women who broke the silence about sexual misconduct and abuse of power by male co-religionists. Using a three-dimensional, ethnoreligious approach that examines gender, ethnicity, and religion, it addresses the relationship between religion and women's experiences and examines both historical contexts and present-day experiences of sexual misconduct within faith communities. This book will be of key interest to students within Gender Studies, History, Religion, and Sociology, clergy and lay religious leaders, and human rights advocates. Keren"--
Keywords: Christian women; Jewish women; MeToo movement; Muslim women; Sexual harassment of women; Social conditions; Women and religion

Sans consentement : trente scandales sexuels qui ont changé le Québec - Morin, Michel (2024)
Depuis l'arrivée de #MoiAussi et des autres mouvements de libération de la parole, on a assisté au Québec à une succession de scandales sexuels impliquant des personnalités publiques, figures respectées et influentes qui avaient abusé de leur pouvoir, parfois des décennies durant. Michel Morin fait un pas de côté pour revisiter ces histoires encore sensibles, en portant une attention particulière à leur traitement médiatique. Avocat de formation, il se penche aussi sur le fonctionnement du système judiciaire et son impact sur le processus de dénonciation. Sans s'ériger en juge, l'auteur laisse parler les faits, bien souvent accablants, dans un essai qui permet de prendre la mesure de ce qui a été trop longtemps ignoré, voire toléré, et du chemin qui reste à parcourir.
Keywords: Bibliographie; Nettoyer

Accueil - Opération cocon (2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Pour des milieux de travail exempts de harcèlement - Ordre des conseillers en ressources humaines et en relations industrielles agréés du Québec. (Carrefour RH, 2024)
Guide pour améliorer ses pratiques de prévention, d'intervention et de soutien dans des situations de harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les artistes remettent en question la distribution de l’argent public en culture - Paré, Étienne (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

RÉZO - Rezo Santé (2024)
RÉZO est un organisme communautaire sans but lucratif montréalais actif depuis 1991 qui offre des services d’éducation et de prévention du VIH et des autres ITSS dans un contexte de promotion de la santé globale, notamment sexuelle, mentale, physique et sociale auprès des hommes GBQ, des autres hommes, et des personnes trans ayant des relations sexuelles avec des hommes.
Keywords: Coffre à outils; À ajouter

Les règlements officiels - Théâtre de la LNI - Théâtre de la LNI (2024)
Il est important de noter qu'il s'agit ici des règles d'origine du Match d'impro. La forme du Match d’impro a évolué et a fait l’objet de certains aménagements au fil des ans. Vous constaterez donc que certaines de ces règles ne correspondent pas à ce que vous avez pu voir lors des plus récents matchs

Mission et historique - Théâtre de la LNI - Théâtre de la LNI (2024)
Mission Réaliser l’impossible Innovation - Collaboration - Dépassement Le Théâtre de la Ligue Nationale d’Improvisation, qui est à la fois un laboratoire et une compagnie phare du théâtre québécois, se consacre à la recherche, la création et la transmission en improvisation théâtrale. La compagnie opte résolument pour une diversité de paroles et d’univers, cherchant avec

Soutien - TransEstrie (TransEstrie, 2024)
Keywords: Coffre à outils; À ajouter

Politique sur le respect des personnes, la prévention et l’intervention en matière de harcèlement - Université du Québec à Montréal (2024)
Keywords: Bibliographie; Nettoyer

Recenser, soutenir, agir - Alix (Alix, 2023)
Alix est là pour te soutenir ainsi que toutes les personnes qui interviennent auprès des personnes LGBTQ+ victimes de violence. Alix t’offre aussi des outils d’informations et de sensibilisation…
Keywords: Coffre à outils; À ajouter

Accounting For the Limited Success of #MeToo in the Popular Music and Stand-Up Comedy Industries - Worden, Chris; Gjika, Anna (Cultural Sociology, 2023)
Despite several high-profile cases and years of #MeToo activism, a lack of systemic change and consistent consequences for many alleged offenders has led journalists and fans to wonder when the popular music and stand-up comedy industries will truly have their ‘MeToo moment.’ In this article, we explain that this moment has already arrived, but has produced inconsistent results in these industries due to the unique cultural and structural obstacles they share, and which frustrate civil sphere actors’ attempts at civil repair. Our analysis draws on Jeffrey C. Alexander’s (2018, 2019) theory of societalization – the process by which institutional crises come to be seen as social problems that demand the intervention of civil sphere actors. We argue that where #MeToo and the popular music and stand-up comedy industries are concerned, the process of societalization has been (and will likely continue to be) ‘blocked’ or ‘stalled’ (Alexander, 2018, 2019). We suggest that the potential for societalization is reduced due to a combination of the arts sphere’s anti-civil values and weak institutionalization in the popular music and stand-up comedy industries.
Keywords: Bibliographie

Capsule sur le GRIP, projet Spotlight (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Capsule Collectif Social - Formation ADISQ (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

L'Aparté - Formation ADISQ (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

Accueil (Centre pour les victimes d’agression sexuelle de Montréal, 2023)
Le CVASM offre un soutien essentiel aux personnes touchées par la violence sexuelle depuis 1980. Trouvez de l'aide dès maintenant.
Keywords: Coffre à outils; À ajouter

Prévenir et gérer le harcèlement - Formations AQPM (Formations : Des classes de perfectionnement pour les professionnel-(le)s de l'industrie audiovisuel, 2023)
« Cette formation permettra aux producteurs et à leurs représentants de reconnaître les situations de harcèlement ou celles qui sont à risque de le devenir afin de comprendre les rôles et responsabilités qui leur reviennent. Les particularités propres à notre industrie y seront également abordées. Formateur: Me Frédéric Massé Borden, Ladner, Gervais »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Écouter, informer, soutenir - Info-aide violence sexuelle (2023)
De l'écoute, du soutien et des références pour les victimes d’agression sexuelle, d’exploitation sexuelle et de toute autre forme de violence sexuelle.

Violences sexuelles: Le plan d’action des festivals - Trépanier, Marilou Bayard (La Presse, 2023)
Les allégations d’intoxication au GHB au Festi-Plage de Cap-d’Espoir, l’an dernier en Gaspésie, ont secoué les festivals partout au Québec. Elles ont aussi servi de bougie d’allumage : alors que les services sont implantés depuis quelques années à Montréal, le milieu festif en région se mobilise pour soutenir les victimes d’agressions et de harcèlement sexuels.

Accusations d’agression sexuelle et de diffamation: Jasmin Roy réplique et poursuit en diffamation Jean-François Robillard - Dussault, Lila (La Presse, 2023)
Un duel de poursuites en diffamation est en cours entre l’acteur Jasmin Roy et un homme qui l’accuse d’agression sexuelle, Jean-François Robillard. L’affaire a pris racine dans la foulée du mouvement #metoo, en 2020. Elle remonte à une soirée dans un bar d’Abitibi-Témiscamingue, 20 ans plus tôt.
Keywords: Bibliographie; Nettoyer

The art of Jane Orleman: childhood trauma and the discourse of sexual violence - Kwon, Hyunji (Journal of Gender Studies, 2023)
Jane Orleman (American, born 1942) is an artist and a survivor of child sexual abuse. Through paintings she created during therapy, Orleman rejects the gendered and patriarchal binaries between therapeutic art and professional art, which pit the private, feminine, and intuitive against the public, masculine, and intellectual. By analysing selected artworks from Orleman that embody her child self, young woman self, and alternative self, I propose that Orleman reflects on and challenges the pathology of sexual trauma along with the discourse of sexual violence as a political statement. Therefore, I argue that her art deserves to be part of a larger, counternarrative, anti-rape and anti-incest cycle in contemporary American art.
Keywords: Sexual violence; art; survivor; therapy; trauma

Le délicat retour d’Éric Lapointe - Lemieux, Marc-André (La Presse, 2023)
Tapis rouge, apparition télé, concerts, nouvelle chanson, sortie d’album… Trois ans après avoir plaidé coupable pour voies de fait contre une femme et s’être éclipsé des grands circuits, Éric Lapointe retrouve, lentement mais sûrement, les projecteurs en 2023. Une opération fragile et non sans écueils possibles.

Un projet pilote pour réduire les risques d’intoxication et pour prévenir la consommation excessive (Éduc'alcool, 2023)
Montréal, le 21 avril 2023 – Éduc’alcool et le Service de police de la Ville de Montréal (SPVM) ont lancé hier le projet pilote Touche pas à mon verre* en présence du ministre de la Sécurité publique du Québec, M. François Bonnardel. Cette initiative prend la forme d’une distribution gratuite de 10 000 protège-verres afin de, notamment, […]
Keywords: Bibliographie; Dans le rapport; Nettoyer

The sound of misogyny: sexual harassment and sexual violence in the music industry - McCarry, Melanie; Käkelä, Emmaleena; Jones, Cassandra; Manoussaki, Kallia (Journal of Gender-Based Violence, 2023)
The cultural and creative industries are the fastest growing industries in the UK (). Stakeholder engagement, media reporting, anecdotal evidence and emerging research suggests that there are endemic levels of sexual harassment and sexualised violence within the music industry that can be described as widespread, systemic and normalised. This article reviews the literature on sexual harassment and sexualised violence in the music industry, examining gender stratifications and inequalities within the music industry with a focus on UK, Australian and US studies. The music industry is not a singular entity but instead, is an agglomeration of many different sub-sectors predominantly consisting of three interconnected spheres of music recording and distribution, music publishing and licensing, and live performance. This paper references Kelly’s (; ; ) theorisations on conducive contexts and the continuum of violence to argue that historical and entrenched misogyny and sexism along with the lack of regulation, process and governing frameworks create conditions for both the maintenance of gender inequality and the perpetuation of sexual harassment and sexualised violence within the music industry. Consequently, both the cultural context and the practice of misogyny (in this case sexual harassment and sexualised violence) within the music industry are mutually supporting and reinforcing.
Keywords: Misogyny; Music; Myriam

Analyse critique du discours en ligne sur les dénonciations de violences à caractère sexuel : le cas de la liste de potentiels agresseurs, Dis son nom - Pelletier, Michela (Université du Québec à Montréal, 2023)
Les fils de commentaires sur Facebook permettent aux internautes de s’exprimer sur différents enjeux. Dans le cadre de ce mémoire, les fils de commentaires sous des articles médiatiques provenant de trois journaux (Journal de Montréal, Le Devoir et La Presse) trainant de la liste de présumés agresseurs Dis son nom ont été analysés. À partir d’une analyse critique de discours, 201 commentaires en réaction à 13 articles médiatiques ont été étudiés afin de répondre à la question de recherche suivante : « Quelles sont les représentations dominantes des dénonciations de violences à caractère sexuel sur les réseaux sociaux dans les commentaires Facebook en réaction aux publications d’articles médiatiques concernant la liste de potentiels agresseurs Dis son nom ? ». De ce fait, l’analyse critique de discours a permis l’étude des représentations dominantes au sein des commentaires Facebook au sujet des dénonciations de violences sexuelles sur les réseaux sociaux. Les résultats de la recherche ont relevé que les discours ont des perspectives davantage négatives au sujet des dénonciations en ligne et que la majorité de ces commentaires ont été partagés par des internautes identifiés comme hommes. L’analyse a illustré que certains commentaires soulignent une transformation et une déconstruction des discours hégémoniques en matière de genre, en permettant notamment une prise de parole émancipatrice. Néanmoins, la plupart des commentaires reproduisent ces discours hégémoniques. L’analyse a également permis de saisir les rapports de pouvoir présents dans les discours, de relever les implicites, les non-dits et les paradoxes, en plus de certains stéréotypes de genre liés aux violences sexuelles au sein des commentaires. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Dis son nom, Facebook, commentaire(s), réseaux sociaux, violences à caractère sexuel, violence(s) de genre, victime(s), #MoiAussi, culture du viol, Analyse critique de discours

Au-delà des « vagues » #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017–2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections, 2023)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant d’abord dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes et ce, au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années (2017–2022). Dans la seconde partie, les autrices détaillent les travaux du réseau D!G , lancé en avril 2021 par Vanessa Blais-Tremblay, et présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ». , This article profiles five organizations that have been advocating for equity in Quebec music since 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL and D!G Différences et inégalités de genre dans la musique au Québec. In line with a long tradition of critical work in feminist historiography, the authors first account for the diversity of feminist mobilizations in Quebec music beyond the #metoo “waves” which have received significant media attention over the past five years (2017–2022). In the second part, the authors detail the development of the D!G network, a feminist collaborative research partnership launched in April 2021 by Vanessa Blais-Tremblay, and its contributions to both Quebec’s music industry and to feminist partnership research epistemologies and methodologies.
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

Plus jamais silencieuses : essai d'activisme social contre l'oppression de genre par la réalisation d'une oeuvre vidéographique documentaire et participative - Pierret, Caroline (Université du Québec à Montréal, 2023)
Tenant compte de l’émergence de la parole et de l’écoute libérées par les médias sociaux lors des mouvements MeToo et de la séquence de dénonciations d’agression à caractère sexuel qui s’ensuivit au Québec comme ailleurs en Occident, comment aujourd’hui un projet artistique peut-il participer à l’affranchissement de la parole et du visage des femmes? Ce mémoire-création explore les notions de silenciation et d’invisibilisation des femmes, en même temps que les possibilités pour elles de s’en libérer en reprenant contact avec leur puissance, notamment par un usage conscient des instruments médiatiques que sont le cinéma, la vidéo, la photographie et la transmission audio. Il décrit différentes méthodologies testées par la réalisation de projets au cours du programme de maîtrise, tous cherchant à comprendre comment, par la captation de voix et de visages, il est possible d’offrir aux femmes une opportunité de réappropriation de leur pouvoir individuel et collectif. Cette recherche-création culmine dans une installation vidéographique documentaire réalisée en collaboration avec dix-neuf Montréalaises originaires de dix pays différents, qui permet de faire vivre aux personnes spectatrices une expérience de rencontre et de leur faire prendre conscience du trouble qui habite l’intérieur des femmes, et ainsi possiblement le leur. Ce faisant, l’oeuvre pose la question cruciale de ce que nous ne voyons pas, n’entendons pas, ne ressentons pas ou n’avons jamais voulu voir, entendre ou ressentir. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : vidéo, documentaire, femmes, silence, parole, écoute, metoo, féminisme, activisme, agentivité.
Keywords: À ajouter

Diversity, Equity, Inclusion & Belonging Committee (ACTRA National, 2023)
ACTRA National’s Diversity, Equity, Inclusion & Belonging Committee promotes the principles concerning the casting of People of Colour, Indigenous Peoples and people with disabilities. The best initiatives are driven by members. We can better shape initiatives to support you by getting to know our membership and understanding your experiences. We welcome your input and your […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023-2026 entre la Guilde des musiciens et musiciennes du Québec et l'Orchestre l'Agora (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023 - 2027 entre la Guilde des musiciens et musiciennes du Québec et l’Orchestre symphonique du Saguenay-Lac-Saint-Jean (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Plan d'action pour les ressources humaines en culture 2023-2028 (Compétence Culture, 2023)

Progress Pride Committee (ACTRA National, 2023)
ACTRA National is proud to be launching the ACTRA National Progress Pride Committee. The inaugural Committee meeting took place on Friday, May 26th, 2023. Mandate The mandate of the committee is to address issues that impact the Queer ACTRA membership across the country, and to build a National community through the sharing of relevant information […]
Keywords: Bibliographie; Dans le rapport

Rebâtir (2023)
Consultation juridique sans frais pour les personnes victimes de violence sexuelle et de violence conjugale.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Réseau d'aide aux hommes pour une société sans violence (À coeur d'homme, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Women's Committee (ACTRA National, 2023)
The best initiatives are driven by members. By getting to know the membership and listening to your experiences, we can better shape initiatives that support you. Does your ACTRA Branch have a Women’s Committee? Find out by contacting your Branch office or contact the National Women’s Committee if you would like to get one started. […]
Keywords: Bibliographie; Dans le rapport

ACTRA By-Laws - ACTRA (2023)
Keywords: Coffre à outils; À ajouter

Harcèlement et inconduites dans le milieu artistique. Quel est mon rôle ? - ADISQ; RIDEAU (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association nationale des éditeurs de livres (ANEL) (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association québécoise de l'indusstrie du disque, du spectacle et de la vidéo (ADISQ) (2023)
Keywords: Bibliographie; Nettoyer

Believability: sexual violence, media, and the politics of doubt - Banet-Weiser, Sarah; Higgins, Kathryn Claire (Polity Press, 2023)

Unsafe words: queering consent in the #MeToo era - Buggs, Shantel Gabrieal; Hoppe, Trevor (Rutgers University Press, 2023)
"What can the #MeToo moment teach queers about consent? And what can queers teach the rest of the world about ethical sex? This radical book brings together academics, activists, artists, and sex workers to tackle dangerous questions about sex, power, consent, and harm.While the authors in this volume are committed to promoting consensual, pleasurable sex, we reject heteronormative, one-size-fits-all models of consent and sexual ethics.#MeToo ushered in an era of reckoning and accountability for one powerful man after another. But too often it has defined sex and harm in starkly heterosexual-and often white and wealthy-terms."Unsafe Words" tells a queerer side of the #MeToo story. Not all of us seek safety in sex. Nor do we all believe "enthusiastic" models of consent are practical or appropriate for some queer communities. We look instead to the tools queer communities have developed themselves to practice ethical sex-from the sex worker negotiating with her client to the gay man having anonymous sex in the backroom. We also consider how queers can better respond to sexual violence. How can our communities do better at responding to and preventing sexual violence?This challenge is especially daunting in a world where the only recourse made available is typically law enforcement, a pillar of American racism, transmisogyny, and homophobia.How can our communities imagine different responses to sexual violence that do not depend on the law to serve justice?The "unsafe words" in this volume challenge dogmatic assumptions about sex and consent while exploring tools and language to promote better, more ethical, and more pleasurable sex for everyone"-- Provided by publisher

3 M$ à Juripop pour venir en aide aux victimes de harcèlement et de violence dans le milieu culturel - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2023)
Keywords: Bibliographie; Dans le rapport; Nettoyer

The other #metoos - Cheema, Iqra Shagufta (Oxford Studies in Gender and International Relations, 2023)
"To bring more awareness to the revolutionary international impact of #MeToo, The Other #MeToos brings together chapters that look at specific iterations of the #MeToo movement across multiple communities, cultures, and countries. Going beyond gender, the book takes into account the intersectional assemblage of location, history, religion, ethnicity, race, class, and neoliberal aspects that inform #MeToo and its place in local and transnational feminisms. From Egypt, Lebanon, Iran, Tunisia, and Morocco to India, Pakistan, Bangladesh, Nepal, and Sri Lanka to South Africa to Latin America to South Korea, Japan, and China to Czech Republic - #MeToo has inspired local movements and hashtag trends as well as transnational and collective hashtags like #MosqueMeToo. Therefore, by making feminism mainstream, it has rendered possible international feminist solidarities unlike any other feminist movement that precedes it. It is critical to document this defining feminist moment of #MeToo and its variants to acknowledge the diversity and multidimensionality of transnational feminisms, along with looking at the various ways they have been changed by the #MeToo, internationally. To that argument, the contributions in this collection examine, analyze, and interrogate the reception, translation, and adaptation of #MeToo in their local, indigenous, minoritized, othered, and/or postcolonial contexts. Overall, The Other #MeToos highlights the adaptation, translation, and impact of #MeToo in non-Western, postcolonial, minoritized, and othered locales to expand the larger discourse and praxes of the #MeToo movement beyond its Americentric focus to explore other feminist possibilities that the movement has enabled"--
Keywords: Feminism; MeToo movement; Sexual harassment of women

Porter plainte: récit - Clermont-Dion, Léa (Le Cheval d'août, 2023)
"Agressée sexuellement par son patron à l'âge de dix-sept ans, Léa Clermont-Dion décide, près d'une décennie plus tard, de poursuivre l'agresseur en justice. Elle consignera son expérience dans son journal jusqu'au procès. Pendant ce temps, l'affaire Harvey Weinstein déclenche le mouvement #MeToo, et des millions de femmes dénoncent la culture du viol à visage découvert. La déposition criante de vérité de Porter plainte témoigne de la froide autorité du droit et des luttes des victimes de crimes sexuels, qui reprennent la parole qu'on leur a soustraite"--Back cover
Keywords: Bibliographie; Nettoyer

Les premier·ères coordonnateurs et coordonnatrices d’intimité certifié·es du Québec - Coordination d'intimité Québec (ICCQ, 2023)
Les coordonnateurs et coordonnatrices d'intimité pour le cinéma et la télévision. Formé·e·s par les programmes de certification qui ont établi le standard du rôle à l'international et ailleurs au Canada, Mo Matton, Stephanie Breton et Mimi Côté représentent la branche du Québec d'Intimacy Coordinato
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Mettre fin au harcèlement sexuel dans le cadre du travail : Se donner les moyens pour agir - Cox, Rachel; Gesualdi-Fecteau, Dalia; Laflamme, Anne-Marie (Comité chargé d'analyser les recours en matière de harcèlement sexuel et d'agressions sexuelles au travail, 2023)
Keywords: Bibliographie; Nettoyer

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

Faire justice: moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Deck Marsault, Elsa (La Fabrique éditions, 2023)
Keywords: Bibliographie; Nettoyer; Restorative justice; Sexual minorities; Violence against; Women

Bureau d'intervention et de prévention - École nationale de cirque - Montréal (École nationale de cirque, 2023)
Le BIP de l'ÉNC vise à prévenir et intervenir en cas de discrimination, de harcèlement et de violence au sein de son établissement.
Keywords: Sophie-Anne

Pollitique contre le harcèlement et l’intimidation et la promotion d’un environnement sain - École nationale de théâtre du Canada (Département du bureau de la direction générale, 2023)
Keywords: Bibliographie; Nettoyer

SPEAK OUT: together for a safer circus - Fédération européenne des écoles de cirque (FEDEC); JUMP (2023)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Working girl: on selling art and selling sex - Giovannitti, Sophia (Verso, 2023)
"Giovannitti argues that if we delve into our anxieties around art and sex, we can find new ways to live and spaces of freedom"--
Keywords: Bibliographie; Nettoyer

Between denunciations and precautions: the #Metoo movement in Quebec. A Critical Discourse Analysis of Quebec newspaper coverage in 2020 and 2017 - Glorieux, Charlotte (Université Charles, 2023)
Keywords: Bibliographie; Nettoyer

Campagne de sensibilisation : Harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2023)
GAIHST Inc est un organisme communautaire de la province de Québec qui vient en aide aux travailleurs et travailleuses ayant subi du harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Répertoire des formations de groupe - Groupe de recherche et d’intervention psychosociale (2023)
«Les formations qu’on offre s’adressent principalement aux professionnel.le.s des milieux scolaires, secondaires et postsecondaires et aux professionnel.le.s de milieux variés où l’information sur les drogues est pertinente (milieux festifs, milieux d’intervention, etc.). Elles peuvent également être offertes directement à la population étudiante des milieux d’éducations postsecondaires (Formation générale aux adultes, formation professionnelle, collégiale ou universitaire). L’approche employée dans la création et l’offre de formation est toujours celle de réduction des méfaits. Nos formations abordent des thèmes tels que les violences à caractère sexuel, le consentement, les effets des substances, la prévention et la réduction des méfaits, les bandelettes de détection de Fentanyl et Naloxone, l’intervention en milieu festif, les drogues et la performance académique, ainsi que de nombreux autres sujets pertinents. »

Can Rainbow Become the New Pink? A study of ballet educators’ responses to the advancement of LGBTQ+ rights - Hawkes, Tracey (Researching Education Bulletin : Creative Arts Special Edition, 2023)
Keywords: Bibliographie; Nettoyer

Étude sur l’expérience des adultes ayant reçu des services dans le cadre d’un processus judiciaire : Dossiers judiciarisés entre juillet 2020 et juin 2022 au Québec concernant une infraction commise dans un contexte de violence conjugale ou sexuelle - Institut de la statistique du Québec (2023)
Keywords: Bibliographie; Nettoyer

Accueil - Juripop (L'Aparté, 2023)
L'Aparté offre des services juridiques gratuits à toute personne ayant vécu du harcèlement dans le milieu de la culture partout au Québec
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collectif social collective - Le Collectif social (Lutte contre les violences sexuelles, 2023)
Offrent des formations sur mesure, ainsi que les formations : - Prévenir la violence sexuelle dans les événements festifs ou sociaux - Les violences sexuelles chez les communautés LGBTQIA2S+ - Devenir un témoin actif
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Check tes chums - Massé, Manon (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

Stratégie en matière de justice autochtone : Ce que nous avons appris Phase 1 de la mobilisation dirigée par le ministère de la Justice Canada - Ministère de la justice Canada (2023)
Keywords: Bibliographie; Nettoyer

Que reste-t-il de nos humours ?À la recherche d’un rire de gauche - Quemener, Nelly (Revue du Crieur, 2023)
Les enjeux liés aux luttes menées par les personnes trans’ sont une parfaite illustration du fait que la visibilité ne suffit pas et qu’elle peut même parfois se révéler préjudiciable. En effet, depuis quelques mois, la presse, la télévision, la radio s’agitent dès qu’une actualité touche de près ou de loin à la transidentité. Actuellement, les voix des trans’ sont encore trop souvent couvertes par les discours cis’, lesquels tendent également à délégitimer les savoirs produits par et pour des trans’. Il est grand temps de retourner la lunette : au lieu de scruter les personnes trans’ – leur transition –, il est urgent de les lire et de les écouter. Ces expériences-là ont certes des choses à apprendre aux personnes cis’ : bien sûr que l’on comprend mieux ce qu’est le genre face à des personnes qui ont fait l’expérience de quitter celui qui leur a été assigné à la naissance, bien sûr que cela rend plus insupportable encore la rigidité des normes de genre, binaires et arbitraires jusqu’à l’absurde. Mais au-delà de ce que les cis’ peuvent apprendre des trans’ pour mieux se comprendre elles-mêmes et eux-mêmes, au-delà de cette lecture instrumentale, il s’agit désormais de laisser les marges parler. Il s’agit de se concentrer sur les luttes sociales, les revendications portées par les personnes trans’ et les associations, de défendre les conditions matérielles d’existence des trans’, de lutter contre les nombreuses discriminations qui pèsent encore sur elles et eux, y compris contre celles qui limitent drastiquement leur accès aux positions permettant de produire légitimement du savoir, il s’agit de les laisser libres de définir leurs cadres de pensée et la manière dont ils, elles, iels souhaitent parler ou pas de leurs parcours. De les laisser, enfin, écrire leur histoire.

Les pratiques des directrices l'industrie de la musique au Québec pour naviguer entre les exigences multiples de leurs fonctions - Saucier, Myriam (Université du Québec à Montréal, 2023)
Keywords: Bibliographie; Nettoyer

En réponse à : « Check ton verre » - Scène & Sauve (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

POLITIQUE ÉDI (ÉQUITÉ, DIVERSITÉ, INCLUSION) - Télé-Québec (2023)
Keywords: Coffre à outils; À ajouter

#metoo: The Good, the Bad, and the Backlash - Tranchese, Alessia (From Fritzl to #metoo: Twelve Years of Rape Coverage in the British Press, 2023)
I start this discussion in this chapter with an outline of the key points within the #metoo debate, looking at what, according to various scholars, has and has not been achieved since the hashtag went viral in 2017. This overview constitutes the context for the subsequent analysis and critical evaluation, which will look at how the press conceptualised #metoo, and how it shaped some of the wider discussions about the hashtag. In Chapter 11, it will focus on whether (and how) the widespread use of #metoo after 2017 affected the representation of violence against women in the British press compared to the previous years.
Keywords: Irina

Comedy’s double killjoy: workers’ DIY strategies to address harassment and precarity in the comedy industry - Trusolino, Madison; Ships, Diandra (Feminist Media Studies, 2023)
Since 2017, the #MeToo movement has highlighted gender-based violence and harassment in the comedy industry, where those comedians affected have little to no workplace infrastructure to lean on. Because comedy clubs are described as venues rather than sites of work, comedy workers are not technically employees and are not protected by workplace safety laws nor supported by professional organizations or unions. We argue that the lack of a formal workplace and its related precarity exacerbates violence against women, queer, transgender, disabled, and/or workers in the Canadian and American comedy industries, pushing comedy workers to enact do-it-yourself workplace safety strategies to protect themselves and one another. We describe these protective, caring activities as akin to Brenda Parker’s “double killjoy,” and push our understanding of creative work into places of public resistance and life-making.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Now About All These Women in the Swedish Film Industry - Wallenberg, Louise; Papadopoulou, Frantzeska; Koskinen, Maaret; Soila, Tytti (Bloomsbury Academic, 2023)
In the aftermath of the MeToo movement, during an ongoing pandemic, and in the midst of repeated demands for a 50/50 split between men and women in above-the-line positions, this book analyzes and interrogates the politics of gender focusing on the Swedish film industry, often considered to be the most "gender equal" film industry worldwide. While this gender equality (with a considerable proportion of women behind the camera) is much due to policies carried out of the state funded Swedish Film Institute, women filmmakers in Sweden still struggle with the same problems as do women in other national film industries. These problems entail having smaller production and distribution budgets than men and working in an environment involving recurring scandals of gender discrimination and sexual harassment. This open access book looks behind the statistics and explores the often complex cultural, legal, and political conditions under which women have entered a male-dominated industry and discusses women’s strategies and efforts to promote change while providing evidence on how women’s presence has challenged the industry by provoking critical reactions and introducing new ways to portray women on screen. Using a wide range of different sources (e.g. archival material, laws, contracts, films, biographical materials, and interviews), the book tells the history of the rise of gender equality efforts undertaken by the Swedish Film Institute and investigates women’s possibilities to manage the rights to their work. It offers compelling portraits of pioneering women who have worked in or in relation to the industry and looks at the experiences of women currently working in the film industry. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Örebro universitet.
Keywords: Irina; Metoo; Sweden; Swedish Film Institute; TV & radio::APF Films; change; cinema::APFA Film theory & criticism; cinema::APFN Film: styles & genres; conditions; discrimination; equality; film industry; filmmakers; male-dominated; pioneering; politics of gender; rights; scandal; sexual harassment

Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

Femmes de spectacle au XIXe siècle - Ponzetto, Valentina; Fix, Florence (2022)
Quelle est la place des femmes dans l’industrie du spectacle du XIXe siècle au-delà des métiers de performance très exposés qu’exercent les actrices, ...
Keywords: Sophie-Anne

#MeToo et la justice réparatrice (Curio.ca, 2022)
Ça fait plus de 5 ans que le mouvement #MeToo (#MoiAussi) a commencé. Depuis, de nombreuses victimes de crimes sexuels critiquent notre système de justice traditionnel. Mais il existe une autre solution, fondée sur des principes et des processus autochtones : la justice réparatrice. Comment fonctionne-t-elle exactement? Tom-Éliot Girard est …
Keywords: Coffre à outils; Nettoyer; À ajouter

La Circassienne: A Study of the Female Circus Artist in French Literature - Menninga, Crystal (Masters Theses, 2022)

Edgar Fruitier est libre après moins d’un mois de prison - Radio-Canada (Radio-Canada, 2022)
Son risque de récidive est jugé faible en raison de son état physique et mental.
Keywords: Bibliographie; Nettoyer

Le mouvement #MoiAussi et ses événements marquants - Pineda, Améli (Le Devoir, 2022)
En octobre 2017 émergeait un mouvement de dénonciation planétaire.
Keywords: Bibliographie; Nettoyer

La littérature après #MoiAussi - Hébert-Dolbec, Anne-Frédérique (Le Devoir, 2022)
Le milieu littéraire attend encore des changements structurels importants, cinq ans après le début du mouvement.
Keywords: Bibliographie; Nettoyer

Politique visant à prévenir et combattre les violences à caractère sexuel - École nationale de théâtre du Canada (2022)
Keywords: Bibliographie; Nettoyer

Une nouvelle accusation contre Eddy Toussaint: Son école de danse change de nom pour se dissocier du chorégraphe - Duhamel, Frédérik-Xavier (La Presse, 2022)
Alors que le chorégraphe Eddy Toussaint fait face à une deuxième accusation d’agression sexuelle, l’école et la troupe de ballet qu’il a fondées prennent leurs distances et changent de nom. Des spectacles ont aussi été retirés de l’affiche dans la foulée des accusations, mais la direction estime qu’il est injuste de pénaliser les danseurs.
Keywords: Bibliographie; Nettoyer

Violences à caractère sexuel: Les actes « graves » de Samuel Archibald - Perron, Louis-Samuel (La Presse, 2022)
L’écrivain réputé Samuel Archibald a profité de son statut de professeur de littérature pour avoir des relations sexuelles avec deux étudiantes sous son autorité, conclut une enquête indépendante commandée par l’Université du Québec à Montréal (UQAM). Une de ces femmes l’accuse même de l’avoir étranglée lors d’une relation sexuelle non consentie. Des actes « graves » et « hostiles » qui ont mené à son départ en catimini de l’UQAM l’an dernier.
Keywords: Bibliographie; Irina; Nettoyer

La relation de pouvoir entre un professeur et ses étudiantes - Radio-Canada (Tout un matin, 2022)
Tout un matin | L'ex-professeur de littérature Samuel Archibald aurait commis des « violences à caractère sexuel » et du « harcèlement sexuel » envers deux étudiantes avec lesquelles il était en situation d'autorité en tant que directeur de maîtrise. Le lien d'emploi entre l'auteur et l'Université du Québec à Montréal (UQAM) aurait été rompu l'année dernière. Au micro de Tout un matin, Rachel Chagnon, professeure au Département des sciences juridiques de l'UQAM, définit ce qu'est une relation de pouvoir entre un enseignant et un étudiant (ce sont majoritairement des femmes), principe qui se trouve au cœur de la politique de l'université pour prévenir et combattre les violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Une présumée victime d’agression sexuelle poursuivie en diffamation pourra rester anonyme - Marin, Stéphanie (Le Devoir, 2022)
Au coeur de la poursuite : une publication dénonçant l’humoriste Alexandre Douville sur la page Dis son nom.
Keywords: Bibliographie; Nettoyer

Allégations d’agressions sexuelles contre Win Butler : des radios boycottent Arcade Fire - ICI.Radio-Canada.ca, Zone Arts- (Radio-Canada, 2022)
Trois femmes font état d’interactions inappropriées, une autre dit avoir été agressée sexuellement en 2015.

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

Sex and safety on set: intimacy coordinators in television drama and film in the VOD and post-Weinstein era - Sørensen, Inge Ejbye (Feminist Media Studies, 2022)
This article examines the work of intimacy coordinators on television drama and film sets and the rise of this new role in the screen industry from a policy and production studies perspective. Since HBO made the employment of an intimacy coordinator mandatory on all productions with scenes of sex, nudity, and physical intimacy in 2018, intimacy coordination has become an industry standard and expectation. Through interviews and analysis of production practices, this article explores how intimacy coordinators change and challenge established production practices on and off set and interrogates the reasons behind the emergence of this role in the screen industry. It situates intimacy coordination in the context of recent industry policies and initiatives that promote equality and diversity, and counter harassment and abuse in the post-Weinstein era. It analyses this role on relation to changing production and distribution models and regimes in the era of VOD portals. The article argues that intimacy coordination is not only a catalyst for reforming practices on set, but a way for the screen industry to negotiate contemporary and historic concerns about sexual harassment and abuse, comply with recent policy and funding requirements, and a mechanism for mitigating economic and reputational risk to productions.
Keywords: #MeToo; Intimacy Coordination; Irina; Prévention; VOD; equality; screen industries

Humoristes cherchent « safe spaces » - Blais-Poulin, Charles-Éric (La Presse, 2022)

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne

Gros été pour la culture du viol - Elkouri, Rima (La Presse, 2022)
Nouveau scandale de viol collectif à Hockey Canada. Allégations d’inconduites sexuelles contre l’humoriste Philippe Bond. Absolution conditionnelle pour l’ingénieur Simon Houle coupable d’agression sexuelle…
Keywords: Bibliographie; Nettoyer

Philippe Bond était déjà sur des listes noires - Bélanger, Cédric (Le Journal de Québec, 2022)
L'humoriste Philippe Bond était déjà depuis plusieurs années sur la liste noire de grandes organisations culturelles.
Keywords: Bibliographie; Nettoyer

Allégations d’agressions et d'inconduites sexuelles visant Julien Lacroix (2022)
Lisez tous nos articles, analyses et opinions sur les allégations d’agressions et d'inconduites sexuelles visant Julien Lacroix. Le Devoir, le quotidien indépendant par excellence au Québec depuis 1910.

Julien Lacroix, Maripier Morin... Le retour des personnalités dénoncées fait mal - Cazzaniga, Constance (Métro, 2022)

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Capsules sur le harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2022)
Le Groupe d’aide et d’information sur le harcèlement au travail (GAIHST) lance 5 capsules vidéo dédiées aux travailleurs(euses) du Québec.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Que fait #MeToo à la littérature ? - Zenetti, Marie-Jeanne (Revue critique de fixxion française contemporaine, 2022)
Que fait #MeToo fait à la lecture, à la critique et à l’enseignement des textes littéraires ? Le mouvement #MeToo a contribué à une large prise de conscience quant aux enjeux linguistiques liés aux violences sexuelles et sexistes : lutter contre de ces violences suppose d’abord de nommer un viol un viol. Mais une telle exigence de désambiguïsation peut entrer en contradiction avec la complexité interprétative valorisée dans le cadre de la lecture littéraire. Elle présenterait par ailleurs le risque d'inviter à lire des textes éloignés de nous dans le temps et l’espace en les évaluant à l’aune de notions et d’une morale contemporaines jugées anachroniques. Prolongeant les réflexions récentes de Gisèle Sapiro (Peut-on dissocier l’œuvre de l’auteur ?) et d’Hélène Merlin-Kajman (La littérature à l’ère de MeToo), cet article étudie la réception du récit de Vanessa Springora, Le consentement (2020). En interrogeant la polarisation des discours critiques et théoriques entre une lecture “féministe” et une lecture “littéraire” parfois présentées comme incompatibles, il pose la question du lien possible entre violences sexuelles et pratiques interprétatives. Il théorise une pratique de lecture soucieuse de contextualiser l’usage des modèles interprétatifs mobilisés dans l’analyse littéraire et de les critiquer en interrogeant les rapports de pouvoir qu’ils dissimulent. Il défend ainsi l’hypothèse que le mouvement #MeToo invite les littéraires à réévaluer leurs pratiques et leurs paradigmes de lecture en fonction de ce qu’ils rendent possible.
Keywords: #metoo; Irina; consentement; lecture féministe; lecture littéraire; violences sexuelles

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Keywords: Bibliographie; Irina; Nettoyer; esports

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Keywords: Irina; diversity; game industry; game studies; inclusion

Caste, gender, and “global Indian-ness”: spaces of safety in stand-up comedy in global Mumbai - James, Aju (Feminist Media Studies, 2022)
This paper argues that stand-up comedy produces the places it uses in the city of Mumbai as “safe” for new middle-class women by excluding Dalit and working-class people who are deemed “dangerous.” Such exclusion is achieved by mobilising places and infrastructure that are built to make Mumbai a “world-class” city, a process that requires the dispossession and exploitation of the masses from which the new middle-class benefits. In the context of the sexual harassment charges that hit the stand-up comedy scene in 2018 and the responses to those charges, I posit that stand-up comedy is a site where “appropriate” gender hierarchies are formulated in the pursuit of “global Indian-ness.”
Keywords: Bibliographie; Global Indian-ness; Mumbai; Nettoyer; Sophie-Anne; sexual harassment; stand-up comedy; world-class city

Poursuite intentée par Gilbert Rozon: La requête de Julie Snyder et Pénélope McQuade rejetée en appel - Morin-Martel, Florence (La Presse, 2022)
La poursuite de Gilbert Rozon réclamant 450 000 $ à Julie Snyder et Pénélope McQuade pour diffamation ira de l’avant. La requête des deux animatrices visant à mettre fin aux procédures, qui relèvent « d’une poursuite-bâillon », selon elles, a été déboutée en Cour d’appel, vendredi.
Keywords: Bibliographie; Nettoyer

Rainbow dancing in Finland and the challenge of transgender inclusion - Kavoura, Anna; Rinne, Santtu (Routledge Handbook of Gender Politics in Sport and Physical Activity, 2022)
Traditionally, partner dances occur between a woman and a man, following rather conservative gender roles and rules. However, as a result of international lesbian, gay, bisexual, transgender, intersex, queer, asexual, allies and more (LGBTIQA+) activism, some social dancing events and competitions have made space for gender and sexual diversity. This chapter focuses on the Rainbow and Same-Sex dancing scene in Finland and its potential and challenges for transgender inclusion. We draw on data collected during the first author’s ethnographic and participatory action research study on trans-inclusive sport spaces and the second author’s experiences as a professional dance teacher and Rainbow trans dancer at both same-sex and mainstream dance competitions. Our findings reveal that the Rainbow dancing movement has helped make dancing more accessible and inclusive for members of the trans community through challenging traditional cis- and heteronormative dance roles and the men-lead/women-follow paradigm. Yet, certain challenges for trans-inclusion persist, such as the transphobic politics and rules of national and international dance associations. In concluding this chapter, we provide recommendations for enhancing access and positive experiences of trans people in dance, DanceSport and sport in general.
Keywords: Bibliographie; Nettoyer

Time for a change: women, work, and gender equality in TV production - Milner, Susan; Gregory, Abigail (Media, Culture & Society, 2022)
This article uses Acker’s concept of inequality regimes to analyze qualitative research findings on work-life balance and gender equality for women in British television production. Female survey respondents, focus group participants, and interviewees spoke of their subjective experience of gendered work practices which disadvantage women as women. These findings build on existing research showing gender disadvantage in the industry, leading to loss of human capital and a narrowing of the range of creative experience. They also show that growing numbers of women are seeking alternative modes of production, at a time of increased awareness of inequality. Such alternatives suggest that change is possible, although it is strongly constrained by organizational logics and subject to continued resistance, in line with Acker’s framework of analysis. Visibility of inequalities is the key to supporting change.
Keywords: Myriam; TV; TV production; Television

Vague de suicides chez les artisans de la scène: Quand le rideau tombe à jamais - Blais-Poulin, Charles-Éric; Groguhé, Marissa (La Presse, 2022)
Keywords: Bibliographie; Nettoyer

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

Entente collective 2022-2024 entre l'Orchestre Métropolitain et la Guilde des musiciens et musiciennes du Québec (2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Personal Safety for Dance (2022)
Personal Safety for Dance exists to develop a dance environment that is free from abuse, open, and supportive for all in dance.
Keywords: Bibliographie; Nettoyer

Soutien psychologique (Guilde des musiciens et musiciennes du Québec, 2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Music as Labour: Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Taylor & Francis, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians’ work is performed, constructed and managed at different times and show that musicians’ working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to ‘be creative’. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.
Keywords: Music; Myriam; Personnel and human resources management; bic Book Industry Communication::A The arts::AV Music; bic Book Industry Communication::K Economics; business & management::KJ Business & management::KJM Management & management techniques::KJMV Management of specific areas::KJMV2 Personnel & human resources management; finance

#MeToo and beyond: perspectives on a global movement - Alcalde, M. Cristina; Villa, Paula-Irene (University Press of Kentucky, 2022)

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts

Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille

Rapport de recherche sur l’éthique en regard des violences à caractère sexuelle dans le milieu de l’humour québécois francophone - Bernier, Dominique; Paré, Christelle; Carbonneau, Karine; Vernus, Judith; Morency, Sophie-Anne (UQÀM et partenaires, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Musicaction, 2022)
Keywords: Bibliographie; Nettoyer

“#UsToo”: Empowerment and Protectionism in Responses to Sexual Abuse of Women with Intellectual Disabilities - Boux, Holly Jeanine (Berkeley Journal of Gender, Law & Justice, 2022)
Keywords: Bibliographie; Nettoyer

Révision des lois sur le statut de l'artiste - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2022)
QUÉBEC, le 3 juin 2022 /CNW Telbec/ - L'Assemblée nationale du Québec a adopté à l'unanimité aujourd'hui le projet de loi numéro 35, Loi visant à moderniser et à harmoniser les règles relatives au statut professionnel de l'artiste, déposé par la ministre...
Keywords: Bibliographie; Nettoyer

Les violences sexistes après #MeToo (Presses des Mines, 2022)
''À partir d'octobre 2017, #MeToo devient un phénomène mondial, en diffusant internationalement le slogan que Tarana Burke, militante new-yorkaise contre les violences sexuelles, avait lancé dix ans plus tôt. Une multitude de victimes témoignent sur divers supports numériques et médiatiques, reformulant et intensifiant des luttes féministes en cours contre les violences sexistes. À l'initiative d'une nouvelle génération de chercheuses et chercheurs francophones sur les violences de genre, ce premier ouvrage académique en France sur #MeToo cherche à comprendre l'événement. Il propose une approche empirique de ce mouvement mondial. Il décrypte d'abord l'événement #MeToo dans sa matérialité, ses contextes de réception et d'appropriation et s'efforce de montrer comment l'usage des réseaux socionumériques permet d'articuler de nouvelles formes de militantisme ou de renforcer des pratiques militantes existantes en ligne et hors ligne. Il inscrit ensuite #MeToo dans une histoire des luttes féministes de plus long terme et s'efforce de questionner son unité à travers l'étude de ses résonances contrastées dans différents milieux professionnels.''-- Site de l'éditeur

Dancing Boys and Men: Negotiating Masculinity and Sexuality - Christofidou, Andria (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Theatrical dance remains widely perceived as an unconventional activity for boys and young men in many Western contexts. This chapter focuses on professional male dancers’ pathways into recreational, pre-professional dance and assesses the various obstacles encountered and the sources of encouragement available to continue dancing and to pursue a dance career. Data analysis challenges the assumption that homophobia and hierarchies among boys, men, and masculinities have been erased. The chapter argues that wider systems of inequality, oppression, and power persist. These continue to affect boys and young men, influencing their choices and the possibilities to transgress gender norms.

Recommandations de l’équipe à l’issue de trois phases d’une programmation de recherche partenariale université/collectivités - Collectif de recherche Justice pour les femmes victimes de violence (Service aux collectivités de l’Université du Québec à Montréal /Fédération des maisons d’hébergement pour femmes / Regroupement des maisons pour femmes victimes de violence conjugale /Concertation des luttes contre l’exploitation sexuelle /Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel, 2022)

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Analysis of the “Regional Survey on Violence and Harassment in the Workplace in the Audiovisual and Performing Arts Industry in Latin America” - FIA-LA; UNI Americas MEI (International Federation of Actors et UNI Americas MEI / Panartes, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Cadre de référence évolutif des objectifs et contenus de prévention des violences à caractère sexuel en milieu d’enseignement supérieur - Fradette-Drouin, Laurie; Bergeron, Manon (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur. Université du Québec à montréal, 2022)
Keywords: Bibliographie; Nettoyer

Loi sur le statut professionnel des artistes des arts visuels, du cinéma, du disque, de la littérature, des métiers d’art et de la scène - Gouvernement du Québec (s-32.1, 2022)

*Loi visant à harmoniser et à moderniser les règles relatives au statut professionnel de l'artiste - Gouvernement du Québec (LQ2022, c 20, 2022)
Keywords: Bibliographie; Nettoyer

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

“My work opportunities depend on how much I can take” : inappropriate behaviour and harassment in the cultural domain in Finland - Jaakola, Meri (2022)
Phenomena of inappropriate behaviour and harassment are neither new nor unique to the cultural domain. However, these phenomena have not been largely publicly discussed before the 2017 me too movement, presumably due to the culture of silence prominent within the cultural domain. After the movement that started from the film industry and quickly spread around the world, discussion on ethical working conditions has arisen within all the cultural domain as well. This qualitative driven mixed methods research reviews the current situation of inappropriate behaviour and harassment in Finland and seeks to understand the magnitude and forms of the phenomena. The research questions are: 1) What special characteristics or structures in the arts and culture field enable inappropriate behaviour and harassment or the possibility of them? And 2) What can be done to eliminate inappropriate behaviour and harassment from arts and culture workplaces? The research questions are answered analyzing research data collected using a survey and six themed interviews. Research data was collected in the spring of 2021. Topics that surfaced from the survey were used as a basis for the interview questions. Findings from the survey and the interviews act as the thematical scope of this master’s thesis, as they are the most important themes to come out of this research. The main findings of the thesis are that there are four elements that enable and maintain the improper working culture within the cultural domain. The elements are insufficient funding, poor management, artist myth, and limitlessness of the work. These themes are examined in discussion with literature. The four steps this thesis suggests helping uproot the improper behaviour in the cultural domain according to the research data and literature are 1) Pushing for the cultural domain’s ethical board to be established, 2) Composing ethical guidelines for all the cultural domain, 3) Basing funding on following the said guidelines, and 4. Talking about improper behaviour publicly and bringing cases of misconduct forward.

Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

Considering Queerness - Actor Training's Issues and Alternatives - LeBlanc, Jacob G. (Université du Commonwealth de Virginie, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Pour une culture du consentement - Les frères Seaborn (2022)
Keywords: Bibliographie; Nettoyer

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Keywords: Bibliographie; Irina; Nettoyer

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

In Her Own Words: Documenting the Current Realities of Women-in-Jazz - Manfredo, Kiernan Steiner, Alexandra (The Routledge Companion to Jazz and Gender, 2022)
Since the inception of jazz, the lives and experiences of women-in-jazz have been inadequately documented and archived, which has led to a lack of female representation in the jazz community. During the recent resurgence of the #MeToo Movement, many women-in-jazz bravely shared stories of sexual discrimination and harassment. As the jazz community continues to address the gender disparity, women’s stories need to be centered in order to address current realities of women-in-jazz. By documenting the experiences of women-in-jazz in higher education as students, educators and performers, sexual discrimination and harassment must be considered as contributing factors of the gender disparity in jazz.
Keywords: Jazz; Music; Myriam

La justice réparatrice en matière de violences sexuelles : L’expérience de dialogue entre personnes victimes et personnes auteures dans les cas de violences sexuelles - Marceau, Laurence (2022)

L'artiste et son oeuvre - McEwen, Jérémie (2022)
Keywords: Bibliographie; Nettoyer

Briser le rideau de verre en humour - Morency, Sophie-Anne; Cézard, Zed; Carbonneau, Karine (2022)
Keywords: Sophie-Anne

Morinom - Office québécois de la langue française (Grand dictionnaire terminologique, 2022)
Prénom qui a été donné à une personne à sa naissance, mais que celle-ci ne souhaite plus qu'on emploie pour la désigner.
Keywords: Bibliographie; Nettoyer

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

Theatre-making in the age of #MeToo: Working cross-culturally toward a framework for making safer creative spaces - Park, Younghee (Université de technologie du Queensland, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Que reste-t-il de #MoiAussi?: secousses québécoises d'un mouvement planétaire - Pineda, Améli (Somme toute : Le Devoir, 2022)
"Au Québec, la vague #MoiAussi qui déferle jusqu'à ce jour a pris son essor les 18 et 19 octobre 2017, lorsque des enquêtes du Devoir et de La Presse ont déboulonné deux géants du monde des médias. C'est avec cet épisode critique que s'ouvre le livre d'Améli Pineda, qui entamait alors sans le savoir plusieurs années de couverture du phénomène des dénonciations d'abus sexuels à grande échelle. À l'intersection des mondes des médias, de la justice et de l'activisme, ce texte synthétise et contextualise les cinq ans du mouvement #MoiAussi au Québec, dépeignant ses plus grands moments et relatant la réaction en chaîne du public et des magistrats. Améli pineda s'appuie sur des articles phares parus depuis 2017 dans Le Devoir ainsi que sur une pléiade d'entrevues menées auprès des protagonistes du mouvement - femmes ayant dénoncé, homme visés par des allégations, avocates et avocats, chercheuses, créatrices de pages de dénonciations virtuelles - ainsi que sur son expérience personnelle de l'effervescence médiatique des cinq dernières années pour trouver un sens à cette prise de conscience collective qui a transformé notre société."--back cover

Dénoncé en ligne, Yann Perreau est lui aussi largué par sa maison de disques - Radio-Canada (Radio-Canada, 2022)
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Raising Their Voices: Independent Review into Sexual Harm, Sexual Harassment, and Systemic Discrimination in the National Music Industry - Shehadie, Alexandra; The Review Team (Support Act, 2022)
Keywords: Bibliographie; Nettoyer

Sex, consent and justice: a new feminist framework - Sikka, Tina (Edinburgh University Press, 2022)

Le privilège de dénoncer: justice pour toutes les victimes de violences sexuelles - Souffrant, Kharoll-Ann (Éditions du remue-ménage, 2022)
Keywords: Bibliographie; Nettoyer

Justice pour les femmes marginalisées victimes de violences sexospécifiques : Ce que la littérature et les intervenantes nous apprennent - Thibault, Sarah; Pagé, Geneviève; Boulebsol, Carole; coll. (Service aux collectivités de l’Université du Québec à Montréal / Fédération des maisons d’hébergement pour femmes / Regroupement des maisons pour femmes victimes de violence conjugale / Concertation des luttes contre l’exploitation sexuelle / Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel., 2022)

Creative Industries in Canada - Thompson, Cheryl; Campbell, Miranda (Canadian Scholars, 2022)
Keywords: Cultural industries.; Irina

Jouer Sur le Banc Les Filles Dans le Monde de L'improvisation. - Walsh-Viau, Emmanuelle.; Joubert, Lucie (Somme Toute, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Plan de lutte contre les violences et le harcèlement sexistes et sexuels dans le spectacle vivant - Ministère de la Culture français (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

The Routledge Companion to Romantic Love - Brooks, Ann (Routledge, 2021)
Keywords: Irina

Politique visant à prévenir et à combattre les violences à caractère sexuel (Annexe E) - École nationale de l'humour (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Why #MeToo Hasn’t Transformed the Stand-Up Scene - Baum, Gary (The Hollywood Reporter, 2021)
Female comics say that the empowerment movement has been met with pushback, retaliation and mockery from male counterparts: “If you’re a woman who’s been harassed, if you just talk about what happened, people perceive you as being some ‘cancel culture’ advocate.”
Keywords: Sophie-Anne

ANNULÉ(E): Réflexions sur la cancel culture - Lussier, Judith (Éditions Cardinal, 2021)
Après On peut plus rien dire, vendu à près de 7 000 exemplaires, Judith Lussier s’attaque à la culture de l’annulation avec son nouveau livre Annulé(e). Un brillant essai d’analyse qui, grâce à de nombreux exemples évocateurs et contemporains, fait le point sur un sujet brûlant d’actualité.« Alors que les réseaux sociaux ont permis à plus d’individus de prendre la parole et à différentes réalités d’être enfin nommées, il semble que le terrain discursif soit de plus en plus miné. Nous n’avons jamais pu autant nous exprimer librement, et pourtant, nous avons le sentiment que communiquer ses idées n’a jamais été aussi complexe et risqué. »C’est avec ce point de départ tout en nuances que la journaliste et essayiste Judith Lussier tente de comprendre la cancel culture. Cet essai examine ce phénomène complexe aux contours flous qui sème parfois la panique et alimente de nombreuses chroniques, sans faire l’économie d’une réflexion sur les dynamiques de pouvoir qui dictent sa trajectoire.
Keywords: Bibliographie; Nettoyer

Un hommage pour Romane Bonnier (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism

Narrating women workers’ perceptions of sexism and change in the Australian screen postproduction sector before and after #MeToo - Dooley, Kath; Erhart, Julia (Feminist Media Studies, 2021)
This article interrogates the localized experiences of present-day workers who identify as women in Australian postproduction sectors, including editing, visual effects (VFX), and animation, exploring sex ism and perceptions of change in the age of #MeToo. Considering the significant numbers of women working in these sectors, and the scant research into their experiences undertaken in an Australian context, the authors conducted semi-structured interviews with ten women in various roles and in various geographical locations in Australia. This qualitative approach to data collection aims to explore inequalities that may not be captured in industry surveys, providing fine-grain details of the ways that individuals in postproduction experience sexism. The resulting data suggests that while there is continuity between the gendered experiences of these workers and that of women in industry sectors that have already been documen ted, there are, however, new observations about changes in work place behavior in the sector, brought about by growing public awareness of industry discrimination and harassment and of shifts in Australian industry policy. The authors isolated recurring themes within women’s gendered experiences in relation to how they per ceived the impact of the gender-equity initiatives on the attitudes of their co-workers, their workplace opportunities, and their experi ences as workers.
Keywords: Irina

Indian Women in Comedy: : An Inquiry into the Perpetuation of Rape Culture on Social Media - Sharma, Mridula (Sanglap: Journal of Literary and Cultural Inquiry, 2021)
‘Postfeminist’ society has created the impression that contemporary discourses on gender representation, particularly in digital media platforms, are pointless. This misconception is coupled with online aggression by men’s rights activists who position feminist debates as sources of male oppression. However, media practices and consumption processes continue to maintain the supremacy of the male gender identity, which strengthens the process of transforming social media into a component of the “manosphere.” The failure of the fourth wave of feminism in utilising the Internet for mobilising activism for the ontological equality of all genders has succeeded by increasing gender-based violence against women. Indian women in comedy negotiate with these systemic inequalities while navigating male dominance in the comedy industry. The paper is an attempt to examine the structures of gender inequality and bias that affect the participation and advancement of women in the comedy circuit. Its focus remains on the formulation of a rape culture on social media and its subsequent consequences in the larger social context of the development of a patriarchal culture.
Keywords: Digital Abuse; Sophie-Anne

“The balance of power is me: 0, Harvey Weinstein: 10”: A Critical Discourse Analysis of the press representation of Hollywood’s biggest sexual harassment scandal - Nikolova, Evelin (Women's Studies International Forum, 2021)
On 5 October 2017, The New York Times published an article in which Harvey Weinstein was accused of sexual harassment by five women. The scandal grew to enormous proportions as more allegations against him followed. This led to the #MeToo and TIME'S UP movements, initiatives to fight sexual harassment in the workplace. Given that media discourse can have an impact on the knowledge, beliefs, attitudes, and behaviours of the public regarding these phenomena (van Dijk 1989), this study adopts a Critical Discourse Studies (CDS) perspective and explores how power and gender inequality are sustained, (re)shaped and/or challenged by focusing on the reporting of the Harvey Weinstein case which - to the author's best knowledge - has not been analysed before in the field of linguistics. It draws from the systemic functional linguistics and the discourse-historical approach and it examines the way the perpetrator, the accusers and the phenomenon of sexual harassment were discursively constructed in five key articles published in the New York Times. The findings differ in a major way from existing research on sexual violence against women in that 1) the perpetrator, Weinstein, was depicted with clear ascription of agency, 2) women victims' voices and feelings were foregrounded, 3) the link between sexual harassment and the social context in which it occurs was discussed.
Keywords: Critical discourse studies; Discourse-Historical Approach; Discursive strategies; Media representation; Myriam; Sexual harassment; Transitivity analysis; Weinstein

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Keywords: Bibliographie; Irina; Nettoyer

Vague de dénonciations : un an après: Qu’est-ce qui cloche dans le milieu culturel ? - Groguhé, Marissa (La Presse, 2021)
C’était il y a un an. En juillet 2020, une nouvelle vague de dénonciations d’agressions et d’inconduites sexuelles a déferlé sur les réseaux sociaux au Québec. Sans être la seule industrie touchée, le milieu culturel a été secoué par plusieurs scandales. Retour sur cet été de grands bouleversements.
Keywords: Bibliographie; Nettoyer

Michel Venne coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2021)
L’ancien journaliste Michel Venne a été reconnu coupable mercredi d’agression et exploitation sexuelle sur Léa Clermont-Dion alors qu’elle avait 17 ans. La poursuite espère que ce verdict encouragera d’autres victimes à porter plainte.
Keywords: Bibliographie; Nettoyer

“Just a Junior Journalist”: Field Theory and Editorial Photographers’ Gendered Experiences - Somerstein, Rachel (Journalism Practice, 2021)
Women outnumber men in graduate and undergraduate programs in photojournalism and work as photo editors at a number of high-profile publications. But in the field of professional editorial photography, they lag men in pay, legitimacy, and status. Using Bourdieu’s field theory, this paper explores how gender shapes the way women experience, compete in, and negotiate the field, specifically regarding assignments, salary, sexual harassment, and tactics for achieving access to stories. Findings suggest that women use their gender as a competitive advantage however they can, but that negative capital attached to femaleness and femininity persists. The findings are based on semi-structured interviews conducted between 2017 and 2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats.
Keywords: Field theory; Myriam; gender; journalism; photojournalism; women and photography

Pourquoi une telle indifférence face au #MeToo de l’édition française ? - Haegel, Mymy (Madmoizelle, 2021)
Ce 21 avril, Mediapart a publié une enquête fouillée relatant des accusations de harcèlement sexuel envers Stéphane Marsan, patron d'une grande maison d'édition. Mais contrairement à d'autres #MeToo, celui-ci n'a pas trouvé beaucoup d'écho...
Keywords: Irina

Normalising sexualised violence in popular culture: eroding, erasing and controlling women in rock music - Hill, Rosemary Lucy; Richards, Daisy; Savigny, Heather (Feminist Media Studies, 2021)
How does music play a role in normalising men’s sexual violence towards women? Using mainstream rock and metal music as an illustrative case study, we offer a nuanced account of the ways in which men’s sexual violence is normalised. Using a definition of sexual violence drawn from Liz Kelly’s notion of a continuum, which reframes sexual violence as the loss of women’s ability to control sexual experiences, we explore the ways in which sexual violence is a prevalent lyrical and audio-visual component of rock and metal songs. We show that a pernicious theme of rock and metal over the last 25 years is the erosion of women’s ability to refuse sexual activity and to have voice and be heard. We argue that this erosion of women’s consent takes place through the representational use of emotional abuse, controlling/coercive behaviour, and through the objectification of women. The erasure of consent presented through these methods becomes a key means of establishing sexual control. Through manipulation, the confusion of what counts as sexual violence and how it is defined, men’s sexual violence against women is normalised.
Keywords: Feminism; music video; rock lyrics; rock music; sexual violence

Creative Control: The Ambivalence of Work in the Culture Industries - Siciliano, Michael L. (Creative Control, 2021)
Michael L. Siciliano draws on nearly two years of ethnographic research as a participant-observer in a Los Angeles music studio and a multichannel YouTube network to explore the contradictions of creative work. Creative Control explains why “cool” jobs help us understand how workers can participate in their own exploitation.
Keywords: Myriam; cognitive capitalism; creative labor; digital media; precarity; sociology of labor

Rachat de Dare To Care par Cœur de pirate : un symbole pour les femmes en musique - Radio-Canada (Radio-Canada, 2021)
La rachat de la maison de disque par Béatrice Martin « a une symbolique très forte ».
Keywords: Bibliographie; Nettoyer

Kesha’s Comeback and the Stakes of Live Performance: Connecting through Trauma at the 2018 Grammy Awards - Hearfield, Katelyn (Journal of Musicological Research, 2021)
The use of live popular music performance as a platform to address gendered and sexual violence and trauma within the popular music industry can be demonstrated through the analysis of Kesha’s performance of “Praying” at the 2018 Grammy Awards. Analyzing the artist’s vocal and artistic delivery, in addition to her public persona following her allegations of sexual abuse against producer Lukasz Gottwald (Dr. Luke), illustrates how live performance—building on and contrasting with social media campaigns, such as #FreeKesha and #MeToo, and studio recordings—is a uniquely effective mode of processing individual and collective trauma.
Keywords: Bibliographie; Nettoyer

Commande un Angelot (2021)
« Le protocole d’accréditation Commande un Angelot a été conçu afin de s’attaquer aux violences à caractère sexuel dans les bars et les événements festifs ou sociaux. Celui-ci vise à prévenir ces situations et à venir en aide aux personnes en difficulté. Le Collectif social, un organisme sans but lucratif qui souhaite déployer et soutenir la réalisation d’initiatives de nature communautaire ou sociale qui répondent aux besoins des communautés étudiantes des établissements d’enseignement supérieur, est derrière ce projet. »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

"Droit au but" pour prévenir les violences subtiles (Parminou: Théâtre socialement engagé, 2021)
Keywords: Bibliographie; Nettoyer

The Change You Want to See: Results of the first-ever survey of workplace sexual harassment in the Canadian performing arts, film, and television industries - Aftermetoo (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

A Balancing Act: Agency and Constraints in University Students’ Understanding of and Responses to Sexual Violence in the Night-Time Economy - Anitha, Sundari; Jordan, Ana; Jameson, Jill; Davy, Zowie (Violence Against Women, 2021)
This article extends our understanding of how university students make sense of, and respond to, sexual violence in the night-time economy (NTE). Based on semi-structured interviews with 26 students in a city in England, we examine students’ constructions of their experiences of sexual violence within the NTE, exploring their negotiations with, and resistance to, this violence. Building upon theories of postfeminism, we interrogate the possibilities for resistance within the gendered spaces of the NTE and propose a disaggregated conceptualization of agency to understand responses to sexual violence, thereby offering useful insights for challenging sexual violence in the NTE and in universities.
Keywords: Camille

Avantage pour membre - Assocation canadienne des humoristes stand-up, Sketch & Impro (AQHS, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Keywords: Bibliographie; Nettoyer

A Gap in the Narrative: Exploring the Experiences of Trans Dancers Today - Best, Erica (Collège Ursinus, 2021)
Keywords: Bibliographie; Nettoyer

Why we lost the sex wars: sexual freedom in the #MeToo era - Bracewell, Lorna N. (University of Minnesota Press, 2021)
"Reexamining feminist sexual politics since the 1970s-the rivalries and the remarkable alliances"--
Keywords: Feminism; MeToo movement; Political aspects; Sex; Sexual harassment

L’opéra, un monde professionnel hanté par les violences de genre - Buscatto, Marie; Helbert, Soline; Roharik, Ionela (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Le 19 août 2020, la soprano Chloé Briot dénonce dans La Lettre du Musicien des agressions sexuelles répétées portées par un collègue chanteur lors de la production de l’opéra L’inondation. Faute d’avoir été entendue et défendue par sa direction, elle annonce encore avoir porté plainte devant la justice française dès le mois de mars de la même année et vouloir ainsi « en finir avec la loi du silence ». Pourquoi l’artiste lyrique n’a-t-elle pas été entendue à plusieurs reprises malgré ses plaintes auprès de ses collègues et de la production ? Dans quelle mesure cette agression sexuelle est-elle symptomatique d’un mode de fonctionnement sexiste plus large du monde de l’opéra français ? Peut-on parler effectivement d’une « loi du silence » dénoncée par la chanteuse ? Si oui, que risquent ceux et celles qui dénonceraient des faits sexistes et des violences sexuelles ?
Keywords: Bibliographie; Nettoyer

Harcèlement au travail - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Formations et autres ressources - Conseil des ressources humaines du secteur culturel (Milieux de travail respectueux dans les arts, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Rebâtir la confiance (Secrétariat à la condition féminine, 2021)

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

Why We Should Avoid Artists Who Cause Harm: Support as Enabling Harm - Elicker, Bradley (Journal of Applied Philosophy, 2021)
This article examines our ethical responsibility toward artists engaged in harmful behaviors. Specifically, I demonstrate when and why we are morally obligated to withdraw our public and financial support from Artists Who Cause Harm such as Louis C.K., Terry Richardson, and Ryan Adams. Using a moral distinction presented by Philippa Foot and others, I identify this support as enabling harm when the wealth and influence that we support removes typical barriers that protect victims from harm and interposes barriers that prevent victims from avoiding harm. I proceed to demonstrate that our personal support is morally significant, and we have a moral responsibility to make contributions to collective action when the cost is low or the degree of belief that others will contribute is high. Here we have both a strong belief that others will withdraw support and a relatively low cost to ourselves to do so. I acknowledge that enabling current harms is only a sufficient condition to withdrawing support from an artist and should not minimize other reasons for avoiding certain artists and their works. However, when we do believe that our support enables an artist engaged in harmful behaviors, we have an obligation to withdraw that support.
Keywords: Bibliographie

The Royal Court in the Wake of #MeToo - Fallow, Catriona; Mullan, Sarah Jane (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Portrait de la pratique de l'improvisation théâtrale en milieu scolaire et plan d'action pour son optimisation - Garneau, Jocelyn (L'escabeau, 2021)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Resistance: righteous rage in the age of #MeToo - Goyette, Sue (University of Regina Press, 2021)
"Writers across the globe speak out against sexual assault and abuse in this powerful new poetry anthology, edited by Sue Goyette. These collected poems from writers across the globe declare one common theme: resistance. By exploring sexual assault and violence in their work, each writer resists the patriarchal systems of power that continue to support a misogynist justice system that supports abusers. In doing so, they reclaim their power and their voice. Created as a response to the Jian Ghomeshi case, writers including Joan Crate, Ashley-Elizabeth Best, and Beth Goobie are, as editor Sue Goyette explains, a "multitude, resisting." The collection could not be more timely. The work adds a new layer to the ever-growing #MeToo movement. Resistance underscores the validity of all women's experiences, and the importance of dignifying such experiences in voice, however that may sound. Because once survivors speak out and disrupt their pain, there is no telling what else they can do."--
Keywords: 2000-2099; 21st century; Canadian poetry; Crimes against; Poetry; Sex crimes; Sexual abuse victims; Violence against; Women

#MeToo: Theatre Women Share Their Stories - Heyliger, Yvette (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

#MeToo In Polish Theatre Education - Kwaśniewska-Mikuła, Monika (Philosophy, Sociology, Psychology and History, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Justice sera-t-elle enfin rendue? Weinstein, Matzneff, Rozon et les autres - Lamartine, Thérèse (M. Éditeur, 2021)
La librairie Gallimard vous renseigne sur Justice sera-t-elle enfin rendue? Weinstein, Matzneff, Rozon et - les autres de l'auteur Lamartine Thérèse (9782924924303). Vous êtes informés sur sa disponibilité, son prix, ses données techniques. Vous pouvez le commander en ajoutant ce livre à votre panier.
Keywords: Coffre à outils; À ajouter

“Frat Boy” Culture: Will the Activision Lawsuit Reform the Gaming Industry? - Lawrence, Kelsey (2021)
Keywords: Irina; games; gaming; industry; lawsuits; sexual harassment; students

T'as juste à porter plainte (2021)
Keywords: Bibliographie; Nettoyer

Krytyczki as Activists: On Theatre Criticism, Affect, Objectivism and #MeToo in Polish Drama Schools: Interview with Monika Kwaśniewska - Lech, Kasia (Critical Stages/Scènes critiques, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Québec, un modèle de « safe space » ? - Léger, Souen (Livres Hebdo, 2021)
Face au #metoo qui a secoué l'édition québécoise à l'été 2020, le milieu littéraire a posé des premiers jalons garantissant des rapports exempts de harcèlement et de violences sexuelles. Une réponse rapide, organisée, qui témoigne de la longueur d'avance prise par le Québec sur les enjeux liés au féminisme et à l'inclusion. De quoi séduire les autrices, françaises notamment. Et donner des idées à la France ?
Keywords: Bibliographie; Nettoyer

Céder n'est pas consentir: une approche clinique et politique du consentement - Leguil, Clotilde (PUF, 2021)

We protect animals well": A structural approach to abusive conduct within circus schools - Matthis, Rosa (Linköping University, 2021)
This master thesis investigates abusive conduct in circus schools. Focus is put on the management level in order to achieve and provide knowledge of measures and attitudes related to prevention. Th ...
Keywords: Bibliographie; Nettoyer; Sophie-Anne

For the Love of Music: Ending Sexual Harassment in the Music Industry - Musicians’ Union (2021)
Keywords: Bibliographie; Nettoyer

Prix Artis : le retrait de la nomination de Maripier Morin confirmé par TVA | Radio-Canada - Radio-Canada (Radio-Canada, 2021)
Keywords: Bibliographie; Nettoyer

A More Pixelated Union: A Look at the Path to Unionization in the Video Game Industry under Trump's National Labor Relations Board - Selfridge, William C. (2021)
Keywords: Irina

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Supporting Brave Spaces for Theatre-​Makers Post-#MeToo: A Chicago-Based Study on Rehearsing and Performing Intimacy in Theatre - Studham, Susan Fenty (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

We Get It: Calling Out Sexism and Harassment in Australia’s Live Performance Industry - Thomasson, Sarah (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Super Fluid/Super Black: Translations and Teachings in Transembodied Metaphysics - Whitson, Ni’Ja (Critical Black Futures: Speculative Theories and Explorations, 2021)
Ni’Ja Whitson turns a piece that was originally commissioned as a keynote lecture for the 2020 Collegium for the African Diaspora Dance (CADD) conference, Fluid Black: Dance Back. This chapter is a hybrid text that centralizes Black Transgender and Nonbinary experiences in a conversation of futurity in African Diasporic spirituality, dance traditions, and performativities. Furthermore, Super Fluid/Super Black interrogates beingness through an exploration of astrophysics and global attempts at Black erasure to uncover new strategies of collectivizing under physical, metaphysical, and cosmic bodies that dismantle cisheteronormativity at their core.

An Examination on Sexual Harassment Activities in the South African Professional Performing Arts Industry - Yende, Sakhiseni Joseph (Journal of African Films & Diaspora Studies, 2021)
Keywords: Bibliographie; Nettoyer; Patriarchal power; Performing arts industry; Professional theatres; Raphaël; Sexual harassment; Women in theatre

Le milieu du jeu vidéo est-il indécrottablement discriminatoire? - Baillargeon, Stéphane (Le Devoir, 2020)
Le mouvement #MoiAussi frappe l’industrie de la manette et son sexisme systémique.
Keywords: Bibliographie; Nettoyer

La musique québécoise à l'ère de #MeToo | UQAM (2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.

Comme une «gifle» au visage des victimes - Pineda, Améli (Le Devoir, 2020)
L’action collective des Courageuses contre Gilbert Rozon a finalement été rejetée par le plus haut tribunal du pays.

Il n'y aura pas d'action collective contre l’ex-producteur Gilbert Rozon - ICI.Radio-Canada.ca, Zone Justice et faits divers- (Radio-Canada, 2020)
La Cour suprême rejette l’appel du groupe Les Courageuses, qui souhaitait entreprendre un tel recours.

Les Courageuses déboutées: « C’est d’une injustice incroyable » - Perron, Louis-Samuel (La Presse, 2020)
« C’est d’une injustice incroyable », lâche Anne-Marie Charette, sous le choc. Comme ses sœurs d’armes, la membre du collectif « Les Courageuses » digère mal le refus de la Cour suprême d’entendre leur appel pour autoriser une action collective contre Gilbert Rozon. Mais pas question de « baisser les bras », assure-t-elle.

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

Politique de prévention du harcèlement psychologique ou sexuel au travail et traitement des plaintes - Théâtre de la Ligue Nationale d'Improvisation (2020)
Keywords: Bibliographie; Nettoyer

Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant) - Service correctionnel Canada (2020)
Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant)
Keywords: Bibliographie; Nettoyer

Milieu littéraire : le harcèlement touche une écrivaine sur trois - UNEQ (union des écrivaines et des écrivains québécois, 2020)
L’Union des écrivaines et des écrivains québécois (UNEQ) révèle les résultats d’une enquête menée auprès des autrices et auteurs québécois début octobre. Ces chiffres démontrent sans équivoque le déséquilibre du rapport de force entre les partenaires du milieu, déséquilibre qui mène bien souvent à des comportements inacceptables et à une omerta intolérable.
Keywords: Bibliographie; Nettoyer

#MeToo in Sweden: Museum Collections, Digital Archiving and Hashtag Visuality - Uimonen, Paula (Ethnos, 2020)
In October 2017, the Nordic Museum in Stockholm launched its #metoo collection. The aim was to capture the viral #MeToo campaign that in Sweden has been likened to a (feminist) revolution. Based on archival research, interviews and media analysis, this article explores public submissions to the #metoo collection and analyses the museum’s rationale for collecting what is considered to be difficult cultural heritage. Noting the absence of images in the collection, the article argues that the iconic hashtag #MeToo constitutes an alternative form of digital visuality, here termed hashtag visuality. Hashtag visuality, the article suggests, is an emerging form of visual representation that captures the multimodal logic of social media, blurring distinctions between texts and images. In Sweden, #MeToo hashtag visuality reveals the contradictory prevalence of structural sexism and sexual violence in a country with a national self-image of gender equality and a self-proclaimed feminist government, while affirming feminist agency.
Keywords: Digital cultural heritage; Myriam; feminist agency; online testimonies; sexual violence; viral campaign

Michel Brûlé reconnu coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2020)
L’éditeur Michel Brûlé a été reconnu coupable mercredi d’agression sexuelle à l’endroit d’une auteure venue le rencontrer pour présenter un manuscrit.
Keywords: Bibliographie; Nettoyer

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

Raport de recherche de l'enquête pièces : violences sexuelles en milieu collégial au Québec - Bergeron, Manon; Gagnon, Audréanne; Blackburn, Marie-Ève; M-Lavoie, Dominique; Paré, Caroline; Roy, Sophie; Szabo, Andrea; Bourget, Claudie (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur, Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Nettoyer

Recommandations - Rudesse (Facebook, 2020)
Keywords: Bibliographie; Dans le rapport; Sophie-Anne

Webinaire contre le harcèlement et les violences (milieu cirque) pour artistes & travailleuses/eurs (2020)
En partenariat avec Juripop, En Piste vous présente le webinaire qui fût présenté dans le cadre de sa clinique contre le harcèlement et les violences dans le milieu cirque, qui a eu lieu le mardi 25 août 2020. Ce webinaire présente les services du Centre d'aide aux victimes d'actes criminels (CAVAC) et du Groupe d'aide et d'information sur le harcèlement sexuel au travail (GAIHST). Pour plus d'information et de ressources, visitez notre site web : www.enpiste.qc.ca
Keywords: Bibliographie; Nettoyer; À ajouter

Vague de dénonciations : au tour du cirque de faire son examen de conscience - Siag, Jean (La Presse, 2020)
Depuis quelques semaines déjà, les témoignages de violences sexuelles dans le monde du cirque se multiplient sur les réseaux sociaux. Au point où le regroupement national des arts du cirque, En Piste, a décidé de lancer dès mardi avec Juripop une clinique « contre le harcèlement et les violences dans le milieu du cirque ». La Presse a parlé aux instigateurs de Victims_Voices_Circus, espace virtuel où la parole de nombreuses artistes s’est fait entendre.
Keywords: Bibliographie; Nettoyer

Allégations d'agressions sexuelles : Julien Lacroix rayé des nominations aux Gémeaux (Radio-Canada.ca, 2020)
Le jeune humoriste a récemment fait l'objet d'allégations d’agressions et d’inconduites sexuelles.

Milieu de l’édition sain et prévention du harcèlement - Association nationale des éditeurs de livres/Québec Édition (2020)
L’ANEL représente des maisons d’édition de langue française du Québec et du Canada. Québec Édition est dédié au rayonnement international du livre québécois et franco-canadien.

Julien Lacroix visé par des allégations d’agressions et d’inconduites sexuelles - Pineda, Améli (Le Devoir, 2020)
Neuf femmes racontent avoir été victimes d'agressions ou d'inconduites sexuelles de la part de l'humoriste et comédien.
Keywords: Bibliographie; Nettoyer

Harcèlement à Ubisoft : la joueuse professionnelle Stéphanie Harvey témoigne - Agence France-Presse (Radio-Canada, 2020)
Une vague de dénonciations secoue Ubisoft et l'industrie du jeu vidéo depuis quelques semaines.
Keywords: Bibliographie; Nettoyer

Me Too: The Effects of Sexual Harassment and Assault in the Entertainment Industry - Gaal, Cassandra (Backstage Pass, 2020)
Keywords: Entertainment Industry; Myriam

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - ICI.Radio-Canada.ca, Zone Arts- (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.

Le milieu littéraire ébranlé par le mouvement de dénonciations - Lapointe, Josée (La Presse, 2020)
Le milieu littéraire fait face lui aussi au mouvement de dénonciations lancé il y a une dizaine de jours. Un groupe de 300 autrices et actrices de la chaîne du livre s’est formé de manière privée pour échanger à propos de cas d’inconduites sexuelles dont beaucoup ont été victimes.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire : il est plus que temps d’agir - UNEQ (Union des écrivaines et des écrivains québécois, 2020)
L’UNEQ donne son appui à la lettre rédigée par un groupe constitué de plusieurs centaines de femmes et minorités de genre déterminées à faire cesser une situation qui ne peut plus durer dans le milieu littéraire.
Keywords: Bibliographie; Nettoyer

Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Cole, Alayna; Zammit, Jessica (CRC Press, 2020)
Description Cooperative Gaming provides context and practical advice regarding diversity in the games industry. The book begins with a deep dive into research literature and the history of diversity in the games industry to provide context around what diversity is and why it is a topic worth considering. The book looks at the different facets of diversity and games, exploring the issues and solutions within game development, studio management, event planning, and more. It provides people with practical advice about being a marginalized person in the games industry and how to be heard, how studios can support inclusive practices, and events can actively become more accessible to a diverse audience. Key Features • Explores the history of diversity in games • Provides important information around what it is like to be a marginalized person in the industry • Gives practical steps to improve the inclusivity of the industry that are designed to aid in contextualizing and upskilling new developers Author Bios Alayna Cole is the managing director of Queerly Represent Me, a not-for-profit championing queer representation in games. Alayna is also a producer at Sledgehammer Games, co-chair of the IGDA LGBTQ+ special interest group, and an award-winning games journalist and game developer. She was featured on the 2016 and 2017 Develop Pacific 30 Under 30 lists and the 2017 and 2019 Develop Pacific Women in Games lists, and she has received several other accolades in the industry. Jessica Zammit started writing in 2013 for Start Select Media, and for the next five years she followed her interest in writing about representations of mental health, diversity, and particularly, sexuality in video games. Jessica has been speaking about diversity in games at conventions such as PAX Australia since 2016 and has been featured on several other discussions in and around the topic of representation in games and games criticism. Along with her co-author, she is co-chair of the IGDA LGBTQ+ special interest group, and she was featured on the 2018 Develop Pacific 30 Under 30 and Women in Games lists.
Keywords: Computers / Programming / Games; Irina

Inconduite sexuelle: deux acteurs largués - Gendron-Martin, Raphaël (Le Journal de Montréal, 2020)
La valse des dénonciations pour inconduite sexuelle touchant le milieu culturel se poursuit.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations: des têtes tombent dans le milieu artistique - Bélanger, Cédric (Le Journal de Québec, 2020)
Les dénonciations font tomber Maripier Morin, Bernard Adamus et le patron de Dare To Care.
Keywords: Bibliographie; Nettoyer

Quand se taire n’est plus une option - Papineau, Philippe; Renaud, Philippe (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Safia Nolin accuse, Maripier Morin s’excuse - Groguhé, Marissa (La Presse, 2020)
L’auteure-compositrice-interprète Safia Nolin a provoqué une onde de choc en accusant mardi Maripier Morin de s’être livrée à du harcèlement sexuel, d’avoir commis une agression physique et d’avoir proféré des propos racistes lors d’une soirée dans un bar il y a deux ans. Des allégations en partie admises par l’animatrice télé, qui a présenté ses excuses le lendemain.
Keywords: Bibliographie; Nettoyer

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

'Urban' no more: black British music execs call for industry reforms (the Guardian, 2020)
Open letter from new group seeks action on racism and better career development

‘To draw light, you need shadow’: Using graphic art to counter gender based violence in Drawing the Line - Zare, Bonnie (South Asian Popular Culture, 2020)
Women in India cope with an ongoing sense of precarity owing to the frequency of street harassment and sexual violence; this impacts their freedom to travel and sense of autonomous agency. The December 2012 Nirbhaya case, the rape and fatal injury of a Delhi medical student, returned the subject of rape to public discourse leading to mass protests and, eventually, some stronger anti-rape laws; however, #metoo allegations surface weekly, and artists and activists are demanding that the trivialization of rape and verbal abuse stop and active steps be taken to dismantle the cultural scaffolding undergirding twomen's violation. In 2014 a collaboration by Zubaan Press (New Delhi) and the Goethe Institute (Germany) brought a group of Indian graphic artists together to create stories about women’s ground realities and the microaggressions they experience. The resulting publication, Drawing the Line: Indian Women Fight Back, contains fourteen vignettes which reveal the constraints women experience and also illuminate women’s capacity for resilience and boldness. This essay analyzes the forms of resistance imagined in these narratives, how particular stories illuminate slow violence, and what may be lost if we know little about the perpetrators who commit these acts against women.
Keywords: Essay; India; Indian women; Myriam; Sexual harassment; Gender; graphic novel; sexuality; violence

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : une recherche en travail social féministe - Robert Durand, Catherine (2020)
L’improvisation théâtrale est une discipline artistique qui est grandement pratiquée, et ce, au Québec comme dans le monde. De manière implicite et explicite, l’une des réflexions qui revient souvent dans ce milieu est celle de la place différente qu’y occupent les femmes en comparaison avec celle de leurs collègues masculins. Les improvisatrices constatent qu’elles ont une place souvent minoritaire, rappelant les inégalités qui se présentent aussi en société pour les femmes. Ce constat n’est pas nouveau mais puisque très peu de recherches portent sur l’improvisation théâtrale, cette question n’a jamais vraiment été explorée. Ce mémoire pose donc les questions de recherche suivantes : Quelle est la place particulière des femmes dans ce milieu ? Quels inégalités et stéréotypes de genre ce milieu véhicule-t-il ? Et, comment les improvisatrices ont-elles le potentiel d’agir sur ces inégalités de genre et de défaire les stéréotypes ? Les objectifs de recherche sont : 1) Recueillir le point de vue des improvisatrices au sujet de leur pratique ; 2) Comprendre la situation particulière des femmes dans ce milieu ; 3) Identifier les stéréotypes et les inégalités de genre véhiculés en improvisation théâtrale ; 4) Relier ces stéréotypes et inégalités de genre à ceux véhiculés en société. Le cadre théorique de ce mémoire est celui du travail social féministe qui s’intéresse notamment aux oppressions et inégalités vécues par les femmes au quotidien, dans « l’ordinaire » de leur vie, ce dont la pratique de l’improvisation théâtrale fait partie. Ancrée dans une méthodologie féministe et qualitative, 8 entretiens semi-dirigés ont été réalisées. L’analyse et la discussion de ces résultats a mis de l’avant l’idée que l’improvisation théâtrale est un espace de reproduction de la socialisation genrée mais aussi un lieu de résistances et donc, plus globalement de négociation entre ces deux pôles. En conclusion, sont soulignés certains nœuds féministes de la recherche et des pistes de solutions pour y pallier. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Féminisme, Improvisation théâtrale, Socialisation genrée, Stéréotypes de genre, Résistances, Recherche féministe, Travail social féministe.

Mobilisations féministes sur Facebook et Twitter: Le cas du mouvement #StopCultureDuViol au Québec - Hübner, Lena A.; Pilote, Anne-Marie (Terminal, 2020)

Comedy in the Era of #MeToo: Masking and Unmasking Sexual Misconduct in Stand-Up Comedy - Oppliger, Patrice; Mears, Kathryn (The Dark Side of Stand-Up Comedy, 2020)
With the announcement of allegations of sexual harassment and sexual assault against beloved comedians, we ask, “Can one separate the art from the artist?” Comedians are supposed to bring audiences joy and laughter; however, this role is challenged when there is incongruity between the comic persona and the real-life misdeeds of comedians. We explore the rise of the #MeToo movement and the role of comedy in exposing as well as masking allegations against Bill Cosby, Louis C.K., Al Franken, and Aziz Ansari. Guided by disposition theory and disengagement models, findings reveal factors of race, gender, and personal relationships appear to influence comedians’ assessment of fellow comedians accused of sexual misconduct. Audience members also appear to experience moral disengagement.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

Non-Consensual Sexual Contact at Electronic Dance Music Parties - Palamar, Joseph J.; Griffin, Marybec (Archives of Sexual Behavior, 2020)
Non-consensual sexual contact in bars is common, but few studies have focused on the extent of this problem at electronic dance music (EDM) parties, which are growing in popularity. We aimed to estimate prevalence and correlates of non-consensual sexual contact among individuals who attend EDM parties in New York City (NYC). Adults (ages 18–40 years) entering EDM parties in NYC were surveyed in 2018 using time–space sampling. Participants (n = 1005) were asked whether they had experienced unwanted or uninvited sexual contact including unwanted groping, kissing, or touching at an EDM party. We estimate that 15.2% of EDM party attendees in NYC have experienced non-consensual sexual contact at such parties. The majority (62.5%) of those reported that it occurred 1–2 times and 49.1% were usually or always drunk or high during the encounter(s). Almost all women experiencing non-consensual contact (99.5%) were all or mostly touched by men; 38.6% of men were all or mostly touched by other men. Women were at more than twice the odds of reporting non-consensual sexual contact than men (aOR = 2.38, p < .05) with 21.8% of women reporting experiencing non-consensual sexual contact compared to 11.0% of men. Among women, those ages 18–24 were at over twice the odds (aOR = 2.75, p < .05) of experiencing non-consensual sexual contact than those ages 25–40. EDM party environments can increase susceptibility to non-consensual sexual contact. Prevention needs to be geared toward those at risk, and education is needed for those likely to commit non-consensual sexual contact.
Keywords: Dance music; Drug use; Non-consensual sex; Sexual assault

Gendered Violence at International Festivals: An Interdisciplinary Perspective - Platt, Louise; Finkel, Rebecca (Routledge, 2020)
Gendered Violence at International Festivals is a groundbreaking collection that focusses on this highly important social issue for the first time. Including a diverse range of interdisciplinary studies on the issue, the book contests the widely held notion that festivals are temporal spaces free from structural sexism, inequalities or gender power dynamics. Rather, they are spaces where these concerns are enhanced and enacted more freely and where the experiential environment is used as an excuse or as an opportunity to victim blame and shame. In this emerging and under-researched area, the chapters not only present original work in terms of topics but also in theoretical and methodological approaches. All of the chapters are cross- or interdisciplinary, drawing on gender, sexualities, cultural and ethnicity studies. Studies from a range of highly regarded academics based around the world examine the subject by looking at examples from a wide range of destinations, including Spain, Argentina, Nigeria, Zimbabwe, Australia, Canada and the UK. This significant book progresses understanding and debates about gendered festival experiences and emphasises the symbolic and physical violence often associated with them. This will be of great interest to, undergraduate and postgraduate students and academics in the field of Events Studies. It will also be of use to practitioners or non-profit workers in the festival industries, including festival management organisations and planning committees.
Keywords: Business & Economics / Industries / Hospitality, Travel & Tourism

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M. (Journalism Practice, 2020)
In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018. “It’s Just art: Auteur Apologism in the Post-Weinstein era”, Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women “testified about the situation in the Swedish music industry”, signing an open letter condemning sexual violence [Nyheter, 2017. “2192 Women in the Swedish Music Industry Behind Appeal Against Sexism.” Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a. “Artists Speak Out Against Sexual Harassment in the Music Industry.” AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month’s coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?
Keywords: Bibliographie; Nettoyer

La Cour d’appel donne raison à Gilbert Rozon - Corriveau, Jeanne (Le Devoir, 2020)
Le tribunal a annulé l’autorisation de l’action collective des Courageuses contre l’ancien magnat de l’humour.
Keywords: Bibliographie; Nettoyer

“These things happen”: Hashtag activism and sexual harassment in the South African film and television industries - Paleker, Gairoonisa (Agenda, 2020)
In August 2017, the South African advocacy group Sisters Working in Film and Television (SWIFT) launched the #ThatsNotOk campaign, which has to date produced six episodes of short films (one episode in two parts, making it seven in total) elucidating the different forms sexual harassment takes, and the different scenarios in which it occurs, in the South African film and television industries. This profile engages with SWIFT and the Public Service Announcement (PSA) films as discursive sites and texts respectively, and provides textual analyses of the PSAs in the context of digital feminism and feminist activism against sexual harassment in the film and television industries. The profile motivates that as expressions of digital feminism, the PSAs critique the pervasiveness and normalisation of sexual harassment, while failing to engage with or critique the neoliberal logic and structure of the film and television industries.
Keywords: #ThatsNotOk; Irina; South African film and television; digital feminism; hashtag activism

Unwanted Sexual Attention in the Night-Time Economy: Behaviors, Safety Strategies, and Conceptualizing “Feisty Femininity” - Gunby, Clare; Carline, Anna; Taylor, Stuart; Gosling, Helena (Feminist Criminology, 2020)
Almost nothing is known about ?unwanted sexual attention? and women?s navigation of it when in bars and nightclubs. Using focus group discussions, this article addresses that gap. It develops knowledge of the behaviors that constitute unwanted, the safety strategies used to manage them, and examines how these practices underpin gender performance in night-time spaces: environments renowned for the dilemmas they pose to women. We then use these data to develop the concept ?feisty femininity? to highlight a neglected form of femininity that overtly resists unwanted encounters. This femininity can arguably play a role in efforts aimed at ending gendered violence.

Aide aux Trans du Québec (Aide aux Trans du Québec, 2020)
Ligne d’écoute et de référenceSans frais : 1 (855) 909-9038, poste 1Nous écrireGroupes de soutien hebdomadaires sur ZoomPour et par les personnes trans, non binaires et en questionnement.Nos services Diapositive précédente Diapositive suivante Notre mission Les buts principaux de l’ATQ sont d’apporter de l’aide et de briser l’isolement des personnes trans, non-binaires et en questionnement.   […]
Keywords: Coffre à outils; À ajouter

Entente collective entre l'Union des artistes et l'Association québécoise de la production médiatique (Artistes interprètes) (2020)
Keywords: Bibliographie; Nettoyer

Best Practices for scenes involving nudity, intimacy, simulated sex and sexual violence - ACTRA (2020)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Land acknowledgment et Equality statement - ACTRA (2020)

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - Bourel, Fanny (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Keywords: Bibliographie; Nettoyer

Le jour où Éric Salvail est tombé - Bourgault-Côté, Guillaume (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Expériences de comportements sexualisés inappropriés, d’agressions sexuelles et de discrimination fondée sur le genre vécues par les travailleurs dans les provinces canadiennes, 2020 - Burczycka, Marta (Statistique Canada, 2020)
Keywords: Bibliographie; Nettoyer

‘Put some balls on that woman’: Gendered repertoires of inequality in screen composers’ careers - Cannizzo, Fabian; Strong, Catherine (Gender, Work & Organization, 2020)
This study contributes to debates about gendered career outcomes in the creative industries using data collected in interviews with Australian screen composers. We identify how gendered inequalities are legitimated through professional norms by comparing the responses of screen composers on barriers to women’s advancement. The article explores how three distinct interpretive repertoires help reproduce the gender inequality regime present in the screen composition field. These repertoires are ‘art vs. equality’, where working towards equality can be framed as antithetical to artistic ideals; ‘gendered music’, where men and women are posited as making fundamentally different types of music; and ‘confidence’, where men are framed as innately possessing certain entrepreneurial skills vital to success in the creative industries, while women both shoulder the blame for not possessing such skills and recognize the risks inherent for them in performing confidence. By focusing on repertoires, this study describes the means by which gender-based discrimination is made overt and offered justification among screen composers, posing challenges to organizations and individuals seeking to address gender inequality in the profession.
Keywords: Australia; Musique de film; Myriam; composers; creative industries; cultural industries; gender inequality; sexism

La musique québécoise à l'ère de #MeToo - Caza, Pierre-Etienne (Actualités UQÀM, 2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

Les personnes victimes d'agressions sexuelles ou de violence conjufale face au système de justice pénale: état de situation - Conseil du statut de la femme (Québec, Conseil du statut de la femme, 2020)

Les personnes victimes d’agressions sexuelles ou de violence conjugale face au système de justice pénale: état de situation - Conseil du statut de la femme (Conseil du statut de la femme, 2020)

Violences sexuelles et abus de pouvoir dans le milieu littéraire: il est plus que temps d’agir - Déclaration commune (Liberté – Art et politique, 2020)
Déclaration commune
Keywords: Bibliographie; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Rapport de recherche sur l'état du milieu du spectacle d'improvisaiton théâtrale au Québec - Garneau, Jocelyn (Le théâtre de la Ligue Nationale d'Improvisation et la Rencontre Théâtre-Ados de Lavac avec l'appui financier du Ministère de la Culture et des Communications du Québec, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Sexual Harassment in the Post-Weinstein World - Grossman, Joanna L. (UC Irvine Law Review, 2020)
Keywords: Myriam; film industry

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention

Can You Come Back from Being Cancelled? A Case Study of Podcasting, Cancel Culture, and Comedians during #MeToo - Holman, Kylie J. (University of Nebraska, 2020)
Cancel culture is a new phenomenon of public shaming, facilitated by social media. This type of public shaming is accepted due to the alleged transgression of those who are cancelled. Social understanding of cancel culture does not generally allow for redemption. Using the theoretical framework of Feminist Media Studies (Van Zoonen, 1994) and Media Framing Theory (Gitlin, 1980), this study reveals the media’s role and power in the cancelling process. This study utilized a mixed-methods approach of case study and text analysis of episodes from the pop culture and politics podcast, Keep It. The case study focused on podcast episodes pertaining to two comedians cancelled for allegations of sexual misconduct in the #MeToo era [Oct. 2017 – Present]: Aziz Ansari and Louis C.K. The study also provided comparative cases of other comedians and comedic actors who were cancelled. Findings add to our understanding of cancel culture and appropriate methods of redemption for those who are cancelled.
Keywords: #MeToo; Bibliographie; Cancel culture; Comedians; Nettoyer; Podcasting; Redemption; Sophie-Anne

Experiencing Male Dominance in Swedish Film Production - Jansson, Maria; Wallenberg, Louise (Women in the International Film Industry: Policy, Practice and Power, 2020)
Sweden has been hailed for its recent success in increasing the number of female directors, scriptwriters and producers. Published reports, panel discussions and a vast number of press conferences on the pressing matter of gender equality within the industry together with a 5050 quota have all put the Swedish film industry—and its CEO Anna Serner—on the map. However, the last couple of years has disclosed several scandals regarding sexism and discrimination in the Swedish film industry—just as in other national film industries. This paper sets out to discuss how female film workers (e.g., directors, actors and producers) understand and negotiate their experiences of male dominance within their work context. Based on a series of interviews with women working in Swedish film from the early 1960s until today, we analyze similarities and differences in experiences as well as how these experiences are explained by the interviewees. Their stories are analyzed by using feminist institutional theory to understand how policy, funding schemes and other institutional aspects are intertwined with their experiences. The paper sets out to analyze three themes: (1) comments and suggestions during production and post-production regarding female protagonists; (2) experience of gender trouble in the process of fundraising; and (3) strategies used by the interviewed filmmakers to produce a more women-friendly environment during productions.
Keywords: Irina

Faire face au harcèlement en milieu de travail culturel: Un rapport sur les mécanismes de dénonciation et d’enquête existants et potentiels pour travailleurs et employeurs culturels - Labine, Lise; LeSage, Jeanne; Gagnon, Grégoire (Conseil des ressources humaines du secteur culturel, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer

Vague de dénonciations : un groupe de soutien est créé dans le milieu littéraire - Larouche, Katy (Radio-Canada, 2020)
Keywords: Bibliographie; Nettoyer

Women in the International Film Industry: Policy, Practice and Power - Liddy, Susan (Springer International Publishing, 2020)
Keywords: Irina

Identity work in female-led creative businesses - Martin, Lynn; Jerrard, Bob; Wright, Lucy (Gender, Work & Organization, 2020)
This study explores the identity work carried out by three female owner-managers in creative industry businesses, identified in Government reports as a discriminatory industrial sector for women in the UK. Through the development of narratives by the owners and other participants, observation of practice and review of online and offline materials, three cases emerged. These showed overlapping, different identities developed and performed through identity work. Each presented rational and logical persona as business leaders despite observation showing extensive use of intuition and gut feeling in both creative and entrepreneurial aspects of the business. Intuition and gut feeling were seen as inappropriate at work as they belonged to the home sphere, emotionally based and therefore automatically unreliable. While occupying male stereotypes and avoiding the female realm of emotion at work, these women expressed femininity through their emphasis on the maternal, ‘being a good mother' as a desired ideal being embedded in work as well as home practice.
Keywords: Myriam; creative industries; entrepreneurship; gender; identity; innovation

Conceptualising safety and crime at UK music festivals: A gendered analysis - Measham, Hannah Bows, Hannah King, Fiona (Gendered Violence at International Festivals, 2020)
There has been a global surge in music festivals over the last decade, especially in Europe. In the UK, it is estimated that more than 3.5 million people attended the 230 music festivals in 2015 (Time Out, 2015; UK Festival Awards, 2016). Despite a body of research indicating higher levels of crime, particularly acquisitive and violent crime in spaces with similar characteristics (e.g. nightclubs, pubs and gigs), there have been no previous studies examining the occurrence or nature of crime at music festivals. This chapter brings together conceptual developments across the social sciences to shed light on the underexplored subject of gender and safety at music festivals, a leisure location of growing interest to social scientists and of significant growth within the events industry. This chapter presents data from the first UK study to explore safety and crime at music festivals and raises questions regarding the distinctive features of commercialised music festivals, the extent to which they can be considered transgressive or countercultural spaces and what might be the distinctions, if any, of gendered sexual violence within such spaces.

The most beautiful job in the world: lifting the veil on the fashion industry - Mensitieri, Giulia; Lehrer, Natasha (Bloomsbury Visual Arts, Bloomsbury Publishing Plc, 2020)
Keywords: Fashion; Myriam

De nouveaux gestes déplacés de musiciens dénoncés - Papineau, Philippe (2020)
Keywords: Bibliographie; Nettoyer

Video Games - Pletcher, Isaac (Communication Technology Update and Fundamentals, 2020)
A video game is an interactive digital entertainment that you “play” on some type of electronic device. The medium has existed in some form since the 1950s, and since that time, has become a major worldwide industry, spawning technology battles and being birthed in new iterations that become ubiquitous parts of modern life. This chapter will look at the development of video games from the beginning, through the golden age, and into the era of the console wars. Further, it will point out the enormous revenues video games make, and show how the #metoo movement and unions are working to change the face of the industry.
Keywords: Irina

Ubisoft : les démissions ne viendront pas à bout de la toxicité, disent des employés - Prévost, Hugo (Radio-Canada, 2020)
Le géant du jeu vidéo est plongé dans la tourmente depuis des semaines en raison d'allégations de harcèlement.
Keywords: Bibliographie; Nettoyer

Dénoncer le harcèlement dans le milieu de l'improvisation - Radio-Canada (D'Est en Est, 2020)
Keywords: Bibliographie; Nettoyer

Cours/Courses - ReadtheCode (2020)
Keywords: Coffre à outils; À ajouter

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : Une recherche en travail social féministe - Robert Durant, Catherine (Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer; Sophie-Anne

Cultural sexism: the politics of feminist rage in the #metoo era - Savigny, Heather (Bristol University Press, 2020)

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Les expériences des victimes de violence sexuelle dans les programmes de justice réparatrice - Wemmers, Jo-Anne; Parent, Isabelle; Casoni, Dianne; Quirion, Marika Lachance (Centre international de criminologie comparée, 2020)
Keywords: Bibliographie; Expérience; Justice; Nettoyer; Système judiciaire; Victimes; Violence

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Keywords: Bibliographie; Nettoyer; Raphaël

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël